Direction-Dependent Effects of White-Matter Conductivity Anisotropy on Modulation Depth and Spatial Extent in Transcranial Interference Stimulation: A Simulation Study - Taiyu Xu; Lian Yu; Xue Li; Qiyong Gong; Neil Roberts; Haoyang Xing (Brain Topography, 2026)

Species-specific light spectrum optimization for coral grow-out - Liam A. Abrams; Nicole D. Fogarty; Hanna R. Koch; Celia Leto; Keri L. O'Neil; Keri Martin; Tyler A. Pratt; Louis-Pierre Rich; Samantha F. Tanguay; Meg Van Horn; Marina Villoch Diaz Maurino; Robert F. Whitehead; et al. (Aquaculture, 2026)

A framework for identifying paper parks - Jessica L. Stewart; Naomi Kingston; Natasha Ali; Heather C. Bingham; Zoe G. Davies; Nigel Dudley; Charlie J. Gardner; Jonas Geldmann; Diego Juffe-Bignoli; Thomas Pienkowski; Rachel E. Sykes; Neil D. Burgess; et al. (Biological Conservation, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

A motley of attitudes: belief, insincerity, and non-doxastic commitment in magical practice - Neil Levy; Robert M. Ross; Ryan McKay (Evolution and Human Behavior, 2026)

Titanium diffusive isotope effects in Fe-bearing basalt - Bruna da Silva Ricardo; Neil R. Bennett; Xu Chu; Robert Webster; Nicolas Greber; Suzette Timmerman; Benjamin J. A. Moulton; Corliss Kin I Sio (Contributions to Mineralogy and Petrology, 2026)

Exercise-induced compensation and C-reactive protein change in adults with elevated C-reactive protein: analysis of a randomised controlled trial - James L. Dorling; John W. Apolzan; Diana M. Thomas; Christoph Höchsmann; Neil M. Johannsen; Robert Ross; Tim S. Church; Corby K. Martin (European Journal of Applied Physiology, 2026)
Purpose Exercise can reduce C-reactive protein (CRP), but heterogeneity exists and it is unclear whether exercise-induced weight compensation occurs or relates to CRP change. We examined whether compensation occurs in adults with elevated CRP during exercise and whether compensation and compensatory behaviours are associated with CRP change. Methods In this 4-month randomised controlled trial, 124 sedentary adults with elevated CRP (mean ± SD: 4.3 ± 2.5 mg/L) were randomised to a control group or a supervised aerobic exercise group expending 16 kcal/kg/week. Predicted weight change was estimated, and weight compensation (weight change – predicted weight change) was calculated. CRP was measured, and energy intake and non-exercise step count were assessed using questionnaires and pedometers, respectively. Results Weight compensation was greater in the exercise group than the control group (1.3 [95% CI, 0.6, 2.1] vs. 0.1 [95% CI, -0.6, 0.9] kg; P = 0.029). In response to exercise, compensation did not differ between participants with moderately higher (≤ 3 mg/L) and higher (> 3 mg/L) CRP ( P = 0.977). Exercisers who did not compensate exhibited a 1.2 (95% CI, 0.2, 2.2) mg/L reduction in CRP versus those who did compensate ( P = 0.016). Higher energy intake was associated with CRP change in exercisers, with each 100 kcal/day elevation in energy intake associated with a 0.1 (95% CI, 0.0, 0.2) mg/L increase in CRP ( P = 0.022). Conclusion Exercise-induced weight compensation occurs in adults with elevated CRP and is associated with attenuated improvements in CRP. Increased energy intake was associated with higher CRP in exercisers, suggesting that limiting increases in energy intake may enhance exercise-induced anti-inflammatory benefits. Clinical trials registration NCT00113061.

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The distribution of mycorrhizal fungi on tree bark correlates with the host preference of the tropical epiphytic orchid Bulbophyllum variegatum on La Réunion island - Rémi Petrolli; Rosa Kemmerling; Géromine Collobert; Eve Hellequin; Tony Robinet; Neil Lancaster; David L. Roberts; Thierry Pailler; Claudine Ah-Peng; Marc-André Selosse; Florent Martos (Fungal Ecology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Reconstructing post‐crisis recovery in the hinterlands of Constantinople: A high‐resolution first‐millennium CE pollen record from Lake Yeniçağa (NW Türkiye) - Cristiano Vignola; Mustafa Doğan; Warren Eastwood; John Haldon; Alessia Masi; Neil Roberts; Çetin Şenkul; Adam Izdebski (Journal of Quaternary Science, 2026)
Facing a novel plague pandemic, military invasions, and political–economic transformations, societies of the eastern Roman (Byzantine) empire had to adapt to a variety of pressures and new ways of exploiting their natural environments during the mid‐1 st millennium CE. As a result, the rural economy of Anatolia transitioned from the intensive mixed‐farming regime of the Graeco‐Roman era to a more varied medieval agricultural system. We reconstruct here for the first time this transition in a region of Anatolia located close to Constantinople through pollen analysis of a sediment core from Lake Yeniçağa, dated to between ~2300 and ~1200 cal a BP. After discussing data for the Hellenistic–Roman era, we document repeated attempts at the recovery of mixed farming during the 6 th to 8 th c. CE. These attempts were only successful toward the end of our study period, with the stabilization of the military situation in the region, as is also visible in the written sources that we analyze in parallel in this paper. Crucially, this model of land exploitation was also constrained by the climatic oscillations that reflected its transitional location between the Aegean, Central Anatolian, and Black Sea climate regions. Thus, our study provides a perfect illustration of the interplay between environment and society in relation to the primary production sector (agriculture), in the dynamic context of a strong elite presence in the nearby capital city.

Comparisons of industrial emission signatures recorded by spheroidal carbonaceous particles and fossil fuel soot from maar lake sediments in Northeastern and Southeastern China - Huijia Zhang; Yongming Han; Yalan Tang; Ulrike Dusek; Dewen Lei; Sarah L. Roberts; Neil L. Rose; Dongna Yan (Environmental Research, 2026)

Relative importance of climate versus socio-environmental development changes to 2050 in rural coastal Bangladesh—a system analysis - Attila N. Lázár; Robert J. Nicholls; Craig W. Hutton; Andres Payo; Helen Adams; Anisul Haque; Derek Clarke; Mashfiqus Salehin; Alistair Hunt; Andrew Allan; W. Neil Adger; M. Munsur Rahman; et al. (Regional Environmental Change, 2026)
Climate change and development are having a profound influence on the integrity of coastal Bangladesh’s people, economy and ecology with climate change widely considered the dominant driver. Our bespoke integrated assessment model (IAM) simulates these changes for rural areas by coupling physical models with economic models, considering shocks like cyclone landfalls, and utilising substantial primary/secondary datasets and stakeholder-derived future scenarios. As such, this study assesses the Bangladesh coastal system’s sensitivity to climate change and policy decisions to 2050. The IAM results suggest that flooding and salinisation have high sensitivity to climatic and environmental drivers, and agricultural productivity is strongly dependent on farming methods and investment in better crop varieties to counteract these changes. Inequality, poverty and GDP per capita are more sensitive to non-climatic drivers. Nonetheless, extreme climatic conditions do impact livelihoods due to economic damage with variable effects across different household types. At least over the next 25 years, development choices (i.e. concrete adaptation actions) will have a similar if not stronger influence on livelihoods and economic wellbeing in rural coastal Bangladesh than climate-driven environmental change. This IAM approach supports decision makers to identify sustainable development pathways that address both current socio-environmental vulnerability as well as develop a more climate-resilient future.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Screening of Brazilian cowpea cultivars for resistance to Meloidogyne incognita and M. javanica - Gerson Luís dos Santos Rodrigues Júnior; Micheline do Amaral Dias; Gabriele Stefanello Manfio; Kaesel Jackson Damasceno e Silva; Juvenil Enrique Cares; Robert Neil Gerard Miller; Jansen Rodrigo Pereira Santos (Crop Protection, 2026)

Climate Change Challenges Grey Wolf Resilience: Insights From Dental Microwear - Amanda A. Burtt; Neil F. Adams; Sabina Nowak; Robert W. Mysłajek; Michal Figura; Mark A. Purnell; Angela L. Lamb; Danielle C. Schreve (Ecology Letters, 2026)
The grey wolf exemplifies ecological resilience, having survived major climatic fluctuations since the Middle Pleistocene. Once the world's most widely distributed mammal, its range has been drastically reduced by human‐driven habitat loss, persecution and competition for resources. Although listed as of Least Concern globally by the IUCN, the omission of climate change as a threat raises critical questions about its future persistence. This study examines dietary flexibility in European grey wolves ( Canis lupus ) using dental microwear texture analysis (DMTA). We compare British Pleistocene wolves from the Last Interglacial (MIS 5e) and the penultimate interglacial (MIS 7a–c) and contemporary wolves from Poland. Results suggest that during periods of elevated global temperatures, wolves exhibit evidence of increased durophagy. These data demonstrate deep‐time dietary plasticity and recurrent behavioural shifts, indicating that while the grey wolf is resilient, future warming winters may significantly reshape wolf diets in the mid‐latitude ecosystems.

Using Multiple Lines of Evidence to Evaluate Spatio-Temporal Trends in Nitrogen Loading to a Eutrophic Estuary - Melanie Hayn; Roxanne Marino; Neil K. Ganju; Robert W. Howarth; Kenneth H. Foreman (Estuaries and Coasts, 2026)
Nitrogen (N) pollution in groundwater in coastal watersheds can have negative impacts on the health of estuaries. West Falmouth Harbor, a shallow lagoon on Cape Cod, MA, USA, has experienced a marked increase in N load since the 1990s due to input from a groundwater aquifer contaminated by a municipal wastewater treatment facility. As part of a broader, long-term research effort to understand the changes to the ecosystem associated with this N input, this study takes an integrative approach at quantifying groundwater N load to the estuary from 1985 through 2024 by combining traditional groundwater well sampling with a wintertime open water mixing model. The latter gives a robust spatially averaged nitrate concentration in discharged groundwater, supplementing the spatial and temporal patterns from the well data. We calculate a conservative estimate for the mean N load to West Falmouth Harbor during peak loading years (2008–2013) of 3.1 mmol m −2 d −1 . This then decreased by approximately 25% by 2024 as a result of wastewater treatment improvements and should continue to decline over the next decade. The long-term trends observed in the groundwater well network complement the open water sampling, providing confidence in the accuracy of the latter approach and allowing us to interpolate an estimate of N loading to West Falmouth Harbor back to 1985. This integrative approach to evaluating groundwater inputs to this ecosystem dramatically improves our ability to quantify total N load and can be a powerful tool for studies in groundwater-fed lagoonal estuaries with a short residence time.

Development of 3D printed microchips with encapsulated channels as miniaturized separation devices for bioanalysis - Christopher T. Desire; R. Dario Arrua; Billy Michalatos; Jing Zhang; Xanthe L. Venn; Michael Breadmore; Zlatko Kopecki; Neil McMillan; Robert Fitridge; Emily F. Hilder; Allison J. Cowin (Analytica Chimica Acta, 2026)

Progress, challenges and future directions in marine organic-walled dinoflagellate cyst research: New insights from an international workshop - Iria García-Moreiras; Ana Amorim; Vera Pospelova; Karin Zonneveld; Donald M. Anderson; Girish Beedessee; Amy Dale; Barrie Dale; Ophélie David; Anne de Vernal; Eugenia Fatourou; Emilie Folie-Boivin; et al. (Marine Micropaleontology, 2025)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Palaeo‐perspectives on anthropogenic soil loss and landscape resilience: An introduction - Neil Roberts; Kevin Walsh (Journal of Quaternary Science, 2025)

Partial desalination as a new paradigm for cultivation of salt-tolerant food crops in hydroponic controlled environment agriculture using brackish waters: A critical review - Jing-Hua Tzeng; David A. Ladner; Clinton Williams; Raghupathy Karthikeyan; W. Shane Walker; Neil Moe; Robert Huehmer; Gary Amy (Desalination, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

2.4–2.3 Ga granitoids of the Arrowsmith orogeny, southwestern Rae craton, Canada: Syn- and post-orogenic magmatism during a global tectono-magmatic lull - Benjamin J.C. Neil; Thomas Chacko; Larry M. Heaman; S. Andy Dufrane; Robert A. Creaser; Edith Martel; Rebecca Canam; D. Graham Pearson (Precambrian Research, 2025)

A Global Account of Established Non‐Native Fish Species - Phillip J. Haubrock; Mariana Novello; Neil Angelo Abreo; Dagmara Błońska; Ana Clara Sampaio Franco; Ismael Soto; Giuseppe Castaldelli; Stelios Katsanevakis; Antonín Kouba; Paride Balzani; Irmak Kurtul; Ali Serhan Tarkan; et al. (Global Change Biology, 2025)
The introduction of non‐native aquatic species has fundamentally transformed aquatic assemblages, primarily due to human activities, such as aquaculture, fisheries enhancement, aquarium trade, the creation of artificial corridors, and deliberate and accidental releases. Despite growing concern for biological invasions, there is no overall global appraisal of successful non‐native fishes. This study compiled a comprehensive dataset from several global sources to examine the taxonomic diversity, geographical distribution, introduction pathways, and ecological impacts of non‐native freshwater and marine fishes. Our dataset includes 1535 established non‐native fish species in 193 countries (82% of the global coverage), with Leuciscidae, Cichlidae, Salmonidae, and Cyprinidae being the most represented families. Although the incline in first reportings appears almost linear, annual reporting has been declining for decades, suggesting fish introduction rates are decreasing. The main introduction pathways are aquarium trade, aquaculture, fishery augmentation, and the creation of artificial corridors. The importance of introduction pathways substantially differed between freshwater species (primarily the aquarium trade and aquaculture) and marine species (corridors). While extensive records exist for hundreds of non‐native fish species, information on their impact types and impact mechanisms remains available only for a third of these species, highlighting broad knowledge deficiencies. Available impact information indicates that non‐native fish species may threaten native biodiversity through primarily competition and predation as dominant mechanisms. The magnitude of highest‐risk invasions suggests remediation is possible through urgent proactive policy and management interventions. This comprehensive global evaluation of established fish species and their ecological effects thus addresses critical data deficiencies, strengthens risk assessment frameworks, and supports the development of targeted biosecurity policies on priority pathways, approaches essential for helping mitigate the environmental and economic impacts of non‐native fish introductions.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Erratum to “Impacts of forest extent, configuration and landscape context on presence of declining breeding Eurasian curlew Numenius arquata and implications for planning new woodland” [For. Ecol. Manag. 572 (2024) 122281] - Roisin E. McGrory; Robert A. Briers; Chris Tomlin; Melanie A. Findlay; Lisa J. Kerslake; Neil Riddle; Patrick J.C. White (Forest Ecology and Management, 2025)

Examining the acute cardiovagal consequences of supine recovery during high-intensity interval exercise - John P. Sasso; Kyla Coates; Liam Stewart; Jinelle Gelinas; Stephen P. Wright; Stephen Seiler; Robert Shave; Neil D. Eves (European Journal of Applied Physiology, 2025)

Environmental drivers of tropospheric bromine and mercury variability in coastal East Antarctica - Neil C. Page; Jenny A. Fisher; Stephen R. Wilson; Robyn Schofield; Robert G. Ryan; Sean Gribben; Andrew R. Klekociuk; Grant C. Edwards; Anthony Morrison (Atmospheric Environment, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Emerging and novel technologies in reproductive and developmental toxicology - Susan E. Maier; Robert M. Cabrera; Yichang Chen; Neil Vargesson (Reproductive Toxicology, 2024)

Impacts of forest extent, configuration and landscape context on presence of declining breeding Eurasian curlew Numenius arquata and implications for planning new woodland - Roisin E. McGrory; Robert A. Briers; Chris Tomlin; Melanie A. Findlay; Lisa J. Kerslake; Neil Riddle; Patrick J.C. White (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Electrical signal transfer characteristics of mycelium-bound composites and fungal fruiting bodies - Neil Phillips; Roshan Weerasekera; Nic Roberts; Antoni Gandia; Andrew Adamatzky (Fungal Ecology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Impact of Various 10-min Cooling Breaks on Internal Body Temperature Responses During Subsequent Intermittent Exercise in the Heat: Application to Tennis - Ayami Yoshihara; Jillian R. O’Neil; Amir M. Defino; Fredy A. Celedon; Ellamarie B. Fox; Robert A. Huggins; Neal R. Glaviano; William M. Adams; Douglas J. Casa; Rebecca L. Stearns (Journal of Science in Sport and Exercise, 2024)

A Wild Arachis Endochitinase Enhances Sclerotinia Resistance in Transgenic Plants - Deziany da Silva Ferreira; Andressa da Cunha Quintana Martins; Pedro Souza Berbert; Renan Miguel dos Anjos; Mario Alfredo de Passos Saraiva; Ana Cristina Miranda Brasileiro; Robert Neil Gerard Miller; Patricia Messenberg Guimaraes (Tropical Plant Biology, 2024)

Passive Removal of Mn from Mine Water Using Oxic Aggregate Beds: Results of Two Pilot Systems - Robert S. Hedin; Neil Wolfe; Benjamin Hedin (Mine Water and the Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Cross-adaptation from heat stress to hypoxia: A systematic review and exploratory meta-analysis - Ashley G.B. Willmott; Alicia G. Diment; Henry C. Chung; Carl A. James; Neil S. Maxwell; Justin D. Roberts; Oliver R. Gibson (Journal of Thermal Biology, 2024)

Tunnel valley formation beneath deglaciating mid-latitude ice sheets: Observations and modelling - James D. Kirkham; Kelly A. Hogan; Robert D. Larter; Neil S. Arnold; Jeremy C. Ely; Chris D. Clark; Ed Self; Ken Games; Mads Huuse; Margaret A. Stewart; Dag Ottesen; Julian A. Dowdeswell (Quaternary Science Reviews, 2024)

The infill of tunnel valleys in the central North Sea: Implications for sedimentary processes, geohazards, and ice-sheet dynamics - James D. Kirkham; Kelly A. Hogan; Robert D. Larter; Ed Self; Ken Games; Mads Huuse; Margaret A. Stewart; Dag Ottesen; Daniel P. Le Heron; Alex Lawrence; Ian Kane; Neil S. Arnold; et al. (Marine Geology, 2024)

Corrigendum to ‘Impacts of offshore oil spill accidents on island bird communities: A test run study around Orkney and Svalbard archipelagos’ [Environ. Pollut. Volume 334 (2023), 122193] - Victor Pavlov; Neil A. James; Elizabeth A. Masden; Victor Cesar Martins de Aguiar; Lars Robert Hole; Henrikki Liimatainen; Eva Pongracz (Environmental Pollution, 2024)

Climate and atmospheric circulation during the Early and Mid‐Holocene inferred from lake‐carbonate oxygen‐isotope records from western Ireland - Jonathan A. Holmes; Julia Tindall; Matthew Jones; Max Holloway; Neil Roberts; Ingo Feeser (Journal of Quaternary Science, 2024)
The Early to Mid‐Holocene experienced marked climate change over the northern hemisphere mid‐latitudes in response to changing insolation and declining ice volume. Oxygen isotopes from lake sediments provide a valuable climate proxy, encoding information regarding temperature, hydroclimate and moisture source. We present oxygen‐isotope records from two lakes in western Ireland that are strongly influenced by the North Atlantic. Excellent replication between the records suggests they reflect regional, not local, influences. Carbonate oxygen‐isotope values peaked at the start of the Holocene, between 11.2 and 11.1 cal ka bp , and then decreased markedly until 6 cal ka bp at both sites. Palaeoecological evidence supports only modest change in temperature or hydroclimate during this interval and we therefore explain the decrease primarily by a reduction in the oxygen‐isotope composition of precipitation (δ 18 O ppt ). We show a similar decrease in δ 18 O values in a forward model of carbonate isotopes between 12–11 and 6–5 cal ka bp. However, the inferred reduction in δ 18 O ppt between the Early and Mid‐Holocene in the model is mainly linked to a decrease in the δ 18 O of the ocean source water from ice sheet melting whereas the lake carbonate isotope records are more consistent with changes in the transport pathway of moisture associated with atmospheric circulation change as the dominant cause.

Allergenicity evaluation of quinoa proteins – A study in Brown Norway rats - Anne-Sofie Ravn Ballegaard; Ana Isabel Sancho; Cui Zhou; Niels-Peter Hell Knudsen; Neil Marcus Rigby; Claus Heiner Bang-Berthelsen; Shashank Gupta; Alan Robert Mackie; Mette Lübeck; Kirsten Pilegaard; Katrine Lindholm Bøgh (Food and Chemical Toxicology, 2023)

Pea aphid odorant-binding protein ApisOBP6 discriminates between aphid sex pheromone components, aphid alarm pheromone and a host plant volatile - Cassie Sims; Michael A. Birkett; Neil J. Oldham; Robert A. Stockman; David M. Withall (Insect Biochemistry and Molecular Biology, 2023)

Impacts of offshore oil spill accidents on island bird communities: A test run study around Orkney and Svalbard archipelagos - Victor Pavlov; Neil A. James; Elizabeth A. Masden; Victor Cesar Martins de Aguiar; Lars Robert Hole; Henrikki Liimatainen; Eva Pongrácz (Environmental Pollution, 2023)

Cultivation of heterotrophic Euglena gracilis: The effects of recycled media on culture growth and associations with growth regulating phytohormone profiles - Alexandra M. Kuhne; Erin N. Morrison; Tamanna Sultana; Anna B. Kisiala; Kathleen Horlock-Roberts; Adam Noble; R. J. Neil Emery (Journal of Applied Phycology, 2023)

Sea level rise adaptation pushes an insular endemic rodent closer to extinction - Paul J. Taillie; Sandra Sneckenberger; Neil Perry; Chad Anderson; Kevin Kalasz; Robert A. McCleery (Biodiversity and Conservation, 2023)
Understanding how species will respond to a rapidly changing global climate is requisite to conserving biodiversity. Though habitat losses from human development and land use change remain the most critical threats to biodiversity globally, some regions, such as low-lying islands, are particularly vulnerable to the effects of climate change. Despite this vulnerability, there may be opportunities for imperiled species on islands to adapt to the effects of climate-induced sea level rise. To understand how the response to rising seas may influence the amount of future habitat, we investigated shifts in the elevational range of the endangered silver rice rat ( Oryzomys palustris natator; hereafter “rice rat”), a species endemic to tidal environments of the Lower Florida Keys, USA. We quantified fine-scale habitat use using radio telemetry of collared animals, first in 2004, and again in 2021, thus spanning a 17-year period during which the local sea level rose by 0.142 m. We observed a shift in the elevational range limits of rice rats which closely mirrored the rise in sea level, and that this apparent ability to adapt to rising sea level decreased the extent of habitat loss in subsequent decades. However, over longer time scales (~ 100 yrs), the extent of habitat loss from sea level rise outpaced rice rats’ ability to adapt. As such, the conservation of biodiversity on low-lying islands hinges on the ability of the global community to decrease anthropogenic greenhouse gas emissions and mitigate the associated consequences for the global climate. Otherwise, conservation practitioners will be increasingly forced to make difficult decisions about how to conserve imperiled species on low-lying islands.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Propagation of electrical signals by fungi - Richard Mayne; Nic Roberts; Neil Phillips; Roshan Weerasekera; Andrew Adamatzky (BioSystems, 2023)

An unprecedented bloom of Lingulodinium polyedra on the French Atlantic coast during summer 2021 - Kenneth Neil Mertens; Michael Retho; Soazig Manach; Maria Laura Zoffoli; Anne Doner; Mathilde Schapira; Gwenael Bilien; Véronique Séchet; Thomas Lacour; Elise Robert; Audrey Duval; Aouregan Terre-Terrillon; et al. (Harmful Algae, 2023)

Pulsed ultraviolet (PUV) disinfection of artificially contaminated seawater seeded with high levels of pathogen disease indicators as an alternative for the shellfish industry depuration systems - Gustavo Waltzer Fehrenbach; Emma Murphy; Robert Pogue; Frank Carter; Eoghan Clifford; Ian Major; Neil Rowan (Environmental Science and Pollution Research, 2023)
The increase in pathogen levels in seawater threatens the safety of entire aquatic ecosystems. Foodborne pathogens can potentially accumulate in shellfish, especially in filter feeders such as bivalves, requiring an efficient depuration process before consumption. Alternative approaches to promote a cost-efficient purge at depuration plants are urgently needed. A small prototype pulsed ultraviolet (PUV) light recirculation system was designed, and its depuration potential was tested in a seawater matrix artificially contaminated with high levels of microbial pathogens Escherichia coli , Staphylococcus aureus , Salmonella typhimurium , Bacillus cereus and Candida albicans . The analysis of treatment parameters including voltage, number of pulses and duration of treatment was performed to ensure the highest reduction in contaminant levels. Optimal PUV disinfection was attained at 60 pulses/min at 1 kV for 10 min (a UV output of 12.9 J/cm 2 ). All reductions were statistically significant, and the greatest was observed for S. aureus (5.63 log 10 ), followed by C. albicans (5.15 log 10 ), S. typhimurium (5 log 10 ), B. cereus (4.59 log 10 ) and E. coli (4.55 log 10 ). PUV treatment disrupted the pathogen DNA with the result that S. aureus , C. albicans and S. typhimurium were not detectable by PCR. Regulations were reviewed to address the applicability of PUV treatment as a promising alternative to assist in the reduction of microbial pathogens at depuration plants due to its high efficiency, short treatment period, high UV dose and recirculation system as currently employed in shellfish depuration plants.

Factors influencing mercury levels in Leach's storm-petrels at northwest Atlantic colonies - Ingrid L. Pollet; Laura McFarlane-Tranquilla; Neil M. Burgess; Antony W. Diamond; Carina Gjerdrum; April Hedd; Rielle Hoeg; Patricia L. Jones; Robert A. Mauck; William A. Montevecchi; Isabeau Pratte; Robert A. Ronconi; et al. (Science of The Total Environment, 2023)

Bio-hydrogen production through microbial electrolysis cell: Structural components and influencing factors - Rahul Gautam; Jagdeep K. Nayak; Neil V. Ress; Robert Steinberger-Wilckens; Uttam Kumar Ghosh (Chemical Engineering Journal, 2023)

Quaternary Science in the time of Covid‐19 - Neil Roberts (Journal of Quaternary Science, 2023)

FOLFIRINOX Pharmacodynamic Interactions in 2D and 3D Pancreatic Cancer Cell Cultures - Taylor J. Allen-Coyle; Jin Niu; Eva Welsch; Neil T. Conlon; Weylon Garner; Martin Clynes; Finbarr O’Sullivan; Robert M. Straubinger; Donald E. Mager; Sandra Roche (The AAPS Journal, 2022)
The multi-drug combination regime, FOLFIRINOX, is a standard of care chemotherapeutic therapy for pancreatic cancer patients. However, systematic evaluation of potential pharmacodynamic interactions among multi-drug therapy has not been reported previously. Here, pharmacodynamic interactions of the FOLFIRINOX agents (5-fluorouracil (5-FU), oxaliplatin (Oxa) and SN-38, the active metabolite of irinotecan) were assessed across a panel of primary and established pancreatic cancer cells. Inhibition of cell proliferation was quantified for each drug, alone and in combination, to obtain quantitative, drug-specific interaction parameters and assess the nature of drug interactions. The experimental data were analysed assuming Bliss independent interactions, and nonlinear regression model fitting was conducted in SAS. Estimates of the drug interaction term, psi (ψ), revealed that the Oxa/SN-38 combination appeared synergistic in PANC-1 (ψ = 0.6, 95% CI = 0.4, 0.9) and modestly synergistic, close to additive, in MIAPaCa-2 (ψ = 0.8, 95% CI = 0.6, 1.0) in 2D assays. The triple combination was strongly synergistic in MIAPaCa-2 (ψ = 0.2, 95% CI = 0.1, 0.3) and modestly synergistic/borderline additive in PANC-1 2D (ψ = 0.8, 95% CI = 0.6, 1.0). The triple combination showed antagonistic interactions in the primary PIN-127 and 3D PANC-1 model (ψ > 1). Quantitative pharmacodynamic interactions have not been described for the FOLFIRINOX regimen; this analysis suggests a complex interplay among the three chemotherapeutic agents. Extension of this pharmacodynamic analysis approach to clinical/translational studies of the FOLFIRINOX combination could reveal additional pharmacodynamic interactions and guide further refinement of this regimen to achieve optimal clinical responses. Graphical abstract

A simplified gravitational reference sensor for satellite geodesy - Anthony Dávila Álvarez; Aaron Knudtson; Unmil Patel; Joseph Gleason; Harold Hollis; Jose Sanjuan; Neil Doughty; Glenn McDaniel; Jennifer Lee; James Leitch; Stephen Bennett; Riccardo Bevilacqua; et al. (Journal of Geodesy, 2022)

Blood identified and quantified in formalin fixed paraffin embedded lung sections using eosin fluorescence - Robert J. Francis; Deborah Ferguson; Sarah Kempster; Joanna Hall; Neil Berry; Kirsty MacLellan-Gibson (Histochemistry and Cell Biology, 2022)
Eosin Y is a common stain in histology. Although usually used for colourimetric imaging where the dye is used to stain pink/red a range of structures in the tissue, Eosin Y is also a fluorochrome, and has been used in this manner for decades. In this study our aim was to investigate the fluorescence properties of the dye to enable quantification of structures within formalin-fixed paraffin-embedded (FFPE) tissue sections. To do this, FFPE sections of hamster tissue were prepared with haematoxylin and eosin Y dyes. Spectral detection on a confocal laser scanning microscope was used to obtain the fluorescence emission spectra of the eosin Y under blue light. This showed clear spectral differences between the red blood cells and congealed blood, compared to the rest of the section. The spectra were so distinct that it was possible to discern these in fluorescence and multi-photon microscopy. An image analysis algorithm was used to quantify the red blood cells. These analyses could have broad applications in histopathology where differentiation is required, such as the analysis of clotting disorders to haemorrhage or damage from infectious disease.

Coastal seascape variability in the intensifying East Australian Current Southern Extension - Lachlan R. Phillips; Neil Malan; Moninya Roughan; Robert Harcourt; Ian Jonsen; Martin Cox; Andrew S. Brierley; David Slip; Adam Wilkins; Gemma Carroll (Frontiers in Marine Science, 2022)
Coastal pelagic ecosystems are highly variable in space and time, with environmental conditions and the distribution of biomass being driven by complex processes operating at multiple scales. The emergent properties of these processes and their interactive effects result in complex and dynamic environmental mosaics referred to as “seascapes”. Mechanisms that link large-scale oceanographic processes and ecological variability in coastal environments remain poorly understood, despite their importance for predicting how ecosystems will respond to climate change. Here we assessed seascape variability along the path of the rapidly intensifying East Australian Current (EAC) Southern Extension in southeast Australia, a hotspot of ocean warming and ecosystem tropicalisation. Using satellite and in situ measures of temperature, salinity and current velocity coupled with contemporaneous measurements of pelagic biomass distribution from nine boat-based active acoustic surveys in five consecutive years, we investigated relationships between the physical environment and the distribution of pelagic biomass (zooplankton and fish) at multiple timescales. Survey periods were characterised by high variability in oceanographic conditions, with variation in coastal conditions influenced by meso-to-large scale processes occurring offshore, including the position and strength of eddies. Intra-annual variability was often of a similar or greater magnitude to inter-annual variability, suggesting highly dynamic conditions with important variation occurring at scales of days to weeks. Two seascape categories were identified being characterised by (A) warmer, less saline water and (B) cooler, more saline water, with the former indicating greater influence of the EAC on coastal processes. Warmer waters were also associated with fewer, deeper and less dense biological aggregations. As the EAC continues to warm and penetrate further south, it is likely that this will have substantial effects on biological activity in coastal pelagic ecosystems, including a potential reduction in the accessibility of prey aggregations to surface-feeding predators and to fisheries. These results highlight the import role of offshore oceanographic processes in driving coastal seascape variability and biological activity in a region undergoing rapid oceanic warming and ecological change.

Phylogeography and population genetics of a widespread cold‐adapted ant, Prenolepis imparis - Maria Adelena Tonione; Ke Bi; Robert R. Dunn; Andrea Lucky; Daniel M. Portik; Neil Durie Tsutsui (Molecular Ecology, 2022)
As species arise, evolve and diverge, they are shaped by forces that unfold across short and long timescales and at both local and vast geographical scales. It is rare, however, to be able document this history across broad sweeps of time and space in a single species. Here, we report the results of a continental‐scale phylogenomic analysis across the entire range of a widespread species. We analysed sequences of 1402 orthologous ultraconserved element (UCE) loci from 75 individuals to identify population genetic structure and historical demographic patterns across the continent‐wide range of a cold‐adapted ant, the winter ant, Prenolepis imparis . We recovered five well‐supported, genetically isolated clades representing lineages that diverged from 8.2–2.2 million years ago. These include: (i) an early diverging lineage located in Florida, (ii) a lineage that spans the southern United States, (iii) populations that extend across the midwestern and northeastern United States, (iv) populations from the western United States and (v) populations in southwestern Arizona and Mexico. Population genetic analyses revealed little or no gene flow among these lineages, but patterns consistent with more recent gene flow among populations within lineages, and localized structure with migration in the western United States. High support for five major geographical lineages and lack of evidence of contemporary gene flow indicate in situ diversification across the species' range, producing relatively ancient lineages that persisted through subsequent climate change and glaciation during the Quaternary.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A stochastic model for estimating sustainable limits to wildlife mortality in a changing world - Oliver Manlik; Robert C. Lacy; William B. Sherwin; Hugh Finn; Neil R. Loneragan; Simon J. Allen (Conservation Biology, 2022)
Human‐caused mortality of wildlife is a pervasive threat to biodiversity. Assessing the population‐level impact of fisheries bycatch and other human‐caused mortality of wildlife has typically relied upon deterministic methods. However, population declines are often accelerated by stochastic factors that are not accounted for in such conventional methods. Building on the widely applied potential biological removal (PBR) equation, we devised a new population modeling approach for estimating sustainable limits to human‐caused mortality and applied it in a case study of bottlenose dolphins affected by capture in an Australian demersal otter trawl fishery. Our approach, termed sustainable anthropogenic mortality in stochastic environments (SAMSE), incorporates environmental and demographic stochasticity, including the dependency of offspring on their mothers. The SAMSE limit is the maximum number of individuals that can be removed without causing negative stochastic population growth. We calculated a PBR of 16.2 dolphins per year based on the best abundance estimate available. In contrast, the SAMSE model indicated that only 2.3–8.0 dolphins could be removed annually without causing a population decline in a stochastic environment. These results suggest that reported bycatch rates are unsustainable in the long term, unless reproductive rates are consistently higher than average. The difference between the deterministic PBR calculation and the SAMSE limits showed that deterministic approaches may underestimate the true impact of human‐caused mortality of wildlife. This highlights the importance of integrating stochasticity when evaluating the impact of bycatch or other human‐caused mortality on wildlife, such as hunting, lethal control measures, and wind turbine collisions. Although population viability analysis (PVA) has been used to evaluate the impact of human‐caused mortality, SAMSE represents a novel PVA framework that incorporates stochasticity for estimating acceptable levels of human‐caused mortality. It offers a broadly applicable, stochastic addition to the demographic toolbox to evaluate the impact of human‐caused mortality on wildlife.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Obituary: Shayne Martin Jacobs (20th April 1971–19th September 2021) - Neil E. Pettit; Neal J. Enright; Karen J. Esler; Will Stock; Robert J. Naiman (Plant Ecology, 2022)

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contribution of social media to cetacean research in Southeast Asia: illuminating populations vulnerable to litter - Amber Coram; Neil Angelo S. Abreo; Robert P. Ellis; Kirsten F. Thompson (Biodiversity and Conservation, 2021)
Litter in the marine environment, in particular plastic, is a significant threat to marine megafauna. Cetaceans are known to ingest or become entangled in marine debris, likely impacting individuals and populations. Southeast Asia is a biodiversity hotspot and harbours a diverse cetacean assemblage. However, there are key knowledge gaps relating to the impact of litter in this region due the lack of experts to survey its vast coastlines. This study aims to address such gaps by using social media, gathering data from Facebook posts relating to cetacean strandings and litter across Southeast Asia between 2009 and 2019. Results show that at least 15 cetacean species have been negatively affected by litter, with ingestion most commonly affecting deep-diving species. Epipelagic and mesopelagic foragers were most vulnerable to entanglement. Davao in the Philippines was identified as a litter-related stranding hotspot. The Irrawaddy dolphin ( Orcaella brevirostris ) and pygmy sperm whale ( Kogia breviceps ) are particularly vulnerable to litter. The combination of social media and peer reviewed literature can help build a more complete picture of the spatial distribution of marine litter and the scale of the impact it has on cetacean populations. In this study we provide details of a valuable online tool for helping to understand the impact of marine litter on cetaceans and other charismatic species that are a focus of community engagement.

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

Novel disease resistance gene paralogs created by CRISPR/Cas9 in soy - Ervin D. Nagy; Julia L. Stevens; Neil Yu; Chris S. Hubmeier; Nona LaFaver; Megan Gillespie; Brian Gardunia; Qianshun Cheng; Steven Johnson; Audrey L. Vaughn; Miguel E. Vega-Sanchez; Mingqui Deng; et al. (Plant Cell Reports, 2021)
Key message Novel disease resistance gene paralogues are generated by targeted chromosome cleavage of tandem duplicated NBS-LRR gene complexes and subsequent DNA repair in soybean. This study demonstrates accelerated diversification of innate immunity of plants using CRISPR. Abstract Nucleotide-binding-site-leucine-rich-repeat (NBS-LRR) gene families are key components of effector-triggered immunity. They are often arranged in tandem duplicated arrays in the genome, a configuration that is conducive to recombinations that will lead to new, chimeric genes. These rearrangements have been recognized as major sources of novel disease resistance phenotypes. Targeted chromosome cleavage by CRISPR/Cas9 can conceivably induce rearrangements and thus emergence of new resistance gene paralogues. Two NBS-LRR families of soy have been selected to demonstrate this concept: a four-copy family in the Rpp1 region (Rpp1L) and a large, complex locus, Rps1 with 22 copies. Copy-number variations suggesting large-scale, CRISPR/Cas9-mediated chromosome rearrangements in the Rpp1L and Rps1 complexes were detected in up to 58.8% of progenies of primary transformants using droplet-digital PCR. Sequencing confirmed development of novel, chimeric paralogs with intact open reading frames. These novel paralogs may confer new disease resistance specificities. This method to diversify innate immunity of plants by genome editing is readily applicable to other disease resistance genes or other repetitive loci.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Sediment Budget Estimates for a Highly Impacted Embayment with Extensive Wetland Loss - Robert J. Chant; David K. Ralston; Neil K Ganju; Cassia Pianca; Amy E. Simonson; Richard A. Cartwright (Estuaries and Coasts, 2021)

Geological evolution of a tectonic and climatic transition zone: the Beyşehir-Suğla basin, lake district of Turkey - Alper Gürbüz; Nizamettin Kazancı; H. Yavuz Hakyemez; Suzanne A. G. Leroy; Neil Roberts; Gerçek Saraç; Zeynep Ergun; Sonay Boyraz-Arslan; Esra Gürbüz; Koray Koç; Özgür Yedek; Tahsin Onur Yücel (International Journal of Earth Sciences, 2021)

Risk factors associated with Ctenocephalides felis flea infestation of peri-urban goats: a neglected parasite in an under-appreciated host - Julia Rose Dahm; Jordana Burdon Bailey; Robert F. Kelly; Patrick Chikungwa; Julius Chulu; Livio Costa Junior; Emily June Freeman; Dagmar Mayer; Stella Mazeri; Neil Donald Sargison (Tropical Animal Health and Production, 2021)
Goats are critical in mixed smallholder agricultural systems in lower and middle-income countries, while fleas are important human and animal health concerns around the world. Convenience sampling was used to describe and consider risk factors for flea infestations of peri-urban goats, with the aim of informing the iterative development of animal husbandry and management based control strategies. Seven hundred and ninety-two goats were examined in 228 households across 10 peri-urban communities surrounding Blantyre in southern Malawi. The prevalence of Ctenocephalides felis fleas was 18.3, 37.1 and 100% at the levels of individual goats, households and communities, respectively, highlighting a neglected human and animal health concern. Constant introduction of new livestock coupled to a lack of biosecurity within communities, the ubiquitous presence of dog and cat hosts for C. felis , the frequency and thoroughness of cleaning overnight goat accommodation, and goat age less than 12 months old were identified as risk factors for flea infestation. This focal cross-sectional study highlights the significance of fleas in peri-urban communities and uncovers trends and commonalities that are needed to inform sustainable disease management. The majority of the peri-urban goat keepers were female, had resided in the same community throughout their whole life and had primary level education. Advice on the planned management of fleas in livestock needs to be tailored towards this demographic group. This approach affords an opportunity to promote public health measures to address household flea infestations and zoonotic disease spread.

A genome‐wide investigation of adaptive signatures in protein‐coding genes related to tool behaviour in New Caledonian and Hawaiian crows - Nicolas Dussex; Verena E. Kutschera; R. Axel W. Wiberg; Darren J. Parker; Gavin R. Hunt; Russell D. Gray; Kim Rutherford; Hideaki Abe; Robert C. Fleischer; Michael G. Ritchie; Christian Rutz; Jochen B. W. Wolf; et al. (Molecular Ecology, 2021)
Very few animals habitually manufacture and use tools. It has been suggested that advanced tool behaviour co‐evolves with a suite of behavioural, morphological and life history traits. In fact, there are indications for such an adaptive complex in tool‐using crows (genus Corvus species). Here, we sequenced the genomes of two habitually tool‐using and ten non‐tool‐using crow species to search for genomic signatures associated with a tool‐using lifestyle. Using comparative genomic and population genetic approaches, we screened for signals of selection in protein‐coding genes in the tool‐using New Caledonian and Hawaiian crows. While we detected signals of recent selection in New Caledonian crows near genes associated with bill morphology, our data indicate that genetic changes in these two lineages are surprisingly subtle, with little evidence at present for convergence. We explore the biological explanations for these findings, such as the relative roles of gene regulation and protein‐coding changes, as well as the possibility that statistical power to detect selection in recently diverged lineages may have been insufficient. Our study contributes to a growing body of literature aiming to decipher the genetic basis of recently evolved complex behaviour.

First insights into the vertical habitat use of the whitespotted eagle ray Aetobatus narinari revealed by pop‐up satellite archival tags - Lauran R. Brewster; Brianna V. Cahill; Miranda N. Burton; Cassady Dougan; Jeffrey S. Herr; Laura Issac Norton; Samantha A. McGuire; Marisa Pico; Elizabeth Urban‐Gedamke; Kim Bassos‐Hull; John P. Tyminski; Robert E. Hueter; et al. (Journal of Fish Biology, 2021)
The whitespotted eagle ray Aetobatus narinari is a tropical to warm‐temperate benthopelagic batoid that ranges widely throughout the western Atlantic Ocean. Despite conservation concerns for the species, its vertical habitat use and diving behaviour remain unknown. Patterns and drivers in the depth distribution of A. narinari were investigated at two separate locations, the western North Atlantic (Islands of Bermuda) and the eastern Gulf of Mexico (Sarasota, Florida, U.S.A.). Between 2010 and 2014, seven pop‐up satellite archival tags were attached to A. narinari using three methods: a through‐tail suture, an external tail‐band and through‐wing attachment. Retention time ranged from 0 to 180 days, with tags attached via the through‐tail method retained longest. Tagged rays spent the majority of time (82.85 ± 12.17% S.D.) within the upper 10 m of the water column and, with one exception, no rays travelled deeper than ~26 m. One Bermuda ray recorded a maximum depth of 50.5 m, suggesting that these animals make excursions off the fore‐reef slope of the Bermuda Platform. Individuals occupied deeper depths (7.42 ± 3.99 m S.D.) during the day versus night (4.90 ± 2.89 m S.D.), which may be explained by foraging and/or predator avoidance. Each individual experienced a significant difference in depth and temperature distributions over the diel cycle. There was evidence that mean hourly depth was best described by location and individual variation using a generalized additive mixed model approach. This is the first study to compare depth distributions of A. narinari from different locations and describe the thermal habitat for this species. Our study highlights the importance of region in describing A. narinari depth use, which may be relevant when developing management plans, whilst demonstrating that diel patterns appear to hold across individuals.

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Addressing inequality and intolerance in human–wildlife coexistence - Neil R. Jordan; Bradley P. Smith; Robert G. Appleby; Lily M. van Eeden; Hugh S. Webster (Conservation Biology, 2020)
Millennia of human conflict with wildlife have built a culture of intolerance toward wildlife among some stakeholders. We explored 2 key obstacles to improved human–wildlife coexistence: coexistence inequality (how the costs and benefits of coexisting with wildlife are unequally shared) and intolerance. The costs of coexisting with wildlife are often disproportionately borne by the so‐called global south and rural communities, and the benefits often flow to the global north and urban dwellers. Attitudes and behaviors toward wildlife (tolerance versus intolerance) vary with social and cultural norms. We suggest more empathetic advocacy is needed that, for example, promotes conservation while appropriately considering those who bear the costs of conflict with wildlife. To achieve more equitable cost‐sharing, we suggest limiting the costs incurred by those most affected or by sharing those costs more widely. For example, we advocate for the development of improved wildlife compensation schemes, increasing the scale of rewilding efforts, and preventing wildlife‐derived revenue leaching out of the local communities bearing the costs of coexistence.

A systematic review of reviews identifying UK validated dietary assessment tools for inclusion on an interactive guided website for researchers: www.nutritools.org - Jozef Hooson (Jzh); Jayne Hutchinson (Jyh); Marisol Warthon-Medina; Neil Hancock; Katharine Greathead; Bethany Knowles; Elisa Vargas-Garcia; Lauren E. Gibson; Linda A. Bush; Barrie Margetts; Sian Robinson; Andy Ness; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Editorial - C. Neil Roberts (Journal of Quaternary Science, 2020)

Magnetic resonance elastography (MRE) shows significant reduction of thigh muscle stiffness in healthy older adults - Paul Kennedy; Eric Barnhill; Calum Gray; Colin Brown; Edwin J.R. van Beek; Neil Roberts; Carolyn Anne Greig (GeroScience, 2020)
Determining the effect of ageing on thigh muscle stiffness using magnetic resonance elastography (MRE) and investigate whether fat fraction and muscle cross-sectional area (CSA) are related to stiffness. Six healthy older adults in their eighth and ninth decade and eight healthy young men were recruited and underwent a 3 T MRI protocol including MRE and Dixon fat fraction imaging. Muscle stiffness, fat fraction and muscle CSA were calculated in ROIs corresponding to the four quadriceps muscles (i.e. vastus lateralis (VL), vastus medialis (VM), vastus intermedius (VI), rectus femoris (RF)), combined quadriceps, combined hamstrings and adductors and whole thigh. Muscle stiffness was significantly reduced ( p < 0.05) in the older group in all measured ROIs except the VI ( p = 0.573) and RF ( p = 0.081). Similarly, mean fat fraction was significantly increased ( p < 0.05) in the older group over all ROIs with the exception of the VI ( p = 0.059) and VL muscle groups ( p = 0.142). Muscle CSA was significantly reduced in older participants in the VM ( p = 0.003) and the combined quadriceps ( p = 0.001), hamstrings and adductors ( p = 0.008) and whole thigh ( p = 0.003). Over the whole thigh, stiffness was significantly negatively correlated with fat fraction ( r = − 0.560, p = 0.037) and positively correlated with CSA ( r = 0.749, p = 0.002). Stepwise regression analysis revealed that age was the most significant predictor of muscle stiffness ( p = 0.001). These results suggest that muscle stiffness is significantly decreased in healthy older adults. Muscle fat fraction and muscle CSA are also significantly changed in older adults; however, age is the most significant predictor of muscle stiffness.

Hippocampal viscoelasticity and episodic memory performance in healthy older adults examined with magnetic resonance elastography - Lucy V. Hiscox; Curtis L. Johnson; Matthew D. J. McGarry; Hillary Schwarb; Edwin J. R. van Beek; Neil Roberts; John M. Starr (Brain Imaging and Behavior, 2020)

Assessing Changes in Airflow and Energy Loss in a Progressive Tracheal Compression Before and After Surgical Correction - Qiwei Xiao; Raul Cetto; Denis J. Doorly; Alister J. Bates; Jan N. Rose; Charlotte McIntyre; Andrew Comerford; Gitta Madani; Neil S. Tolley; Robert Schroter (Annals of Biomedical Engineering, 2020)
The energy needed to drive airflow through the trachea normally constitutes a minor component of the work of breathing. However, with progressive tracheal compression, patient subjective symptoms can include severe breathing difficulties. Many patients suffer multiple respiratory co-morbidities and so it is important to assess compression effects when evaluating the need for surgery. This work describes the use of computational prediction to determine airflow resistance in compressed tracheal geometries reconstructed from a series of CT scans. Using energy flux analysis, the regions that contribute the most to airway resistance during inhalation are identified. The principal such region is where flow emerging from the zone of maximum constriction undergoes breakup and turbulent mixing. Secondary regions are also found below the tongue base and around the glottis, with overall airway resistance scaling nearly quadratically with flow rate. Since the anatomical extent of the imaged airway varied between scans—as commonly occurs with clinical data and when assessing reported differences between research studies—the effect of sub-glottic inflow truncation is considered. Analysis shows truncation alters the location of jet breakup and weakly influences the pattern of pressure recovery. Tests also show that placing a simple artificial glottis in the inflow to a truncated model can replicate patterns of energy loss in more extensive models, suggesting a means to assess sensitivity to domain truncation in tracheal airflow simulations.

Surfactant Foam Selection for Enhanced Light Non-Aqueous Phase Liquids (LNAPL) Recovery in Contaminated Aquifers - Mélanie Longpré-Girard; Richard Martel; Thomas Robert; René Lefebvre; Jean-Marc Lauzon; Neil Thomson (Transport in Porous Media, 2020)

Multi‐century trends to wetter winters and drier summers in the England and Wales precipitation series explained by observational and sampling bias in early records - Conor Murphy; Robert L. Wilby; Tom K. R. Matthews; Peter Thorne; Ciaran Broderick; Rowan Fealy; Julia Hall; Shaun Harrigan; Phil Jones; Gerard McCarthy; Neil MacDonald; Simon Noone; et al. (International Journal of Climatology, 2020)
Globally, few precipitation records extend to the 18th century. The England Wales Precipitation (EWP) series is a notable exception with continuous monthly records from 1766. EWP has found widespread use across diverse fields of research including trend detection, evaluation of climate model simulations, as a proxy for mid‐latitude atmospheric circulation, a predictor in long‐term European gridded precipitation data sets, the assessment of drought and extremes, tree‐ring reconstructions and as a benchmark for other regional series. A key finding from EWP has been the multi‐centennial trends towards wetter winters and drier summers. We statistically reconstruct seasonal EWP using independent, quality‐assured temperature, pressure and circulation indices. Using a sleet and snow series for the UK derived by Profs. Gordon Manley and Elizabeth Shaw to examine winter reconstructions, we show that precipitation totals for pre‐1870 winters are likely biased low due to gauge under‐catch of snowfall and a higher incidence of snowfall during this period. When these factors are accounted for in our reconstructions, the observed trend to wetter winters in EWP is no longer evident. For summer, we find that pre‐1820 precipitation totals are too high, likely due to decreasing network density and less certain data at key stations. A significant trend to drier summers is not robustly present in our reconstructions of the EWP series. While our findings are more certain for winter than summer, we highlight (a) that extreme caution should be exercised when using EWP to make inferences about multi‐centennial trends, and; (b) that assessments of 18th and 19th Century winter precipitation should be aware of potential snow biases in early records. Our findings underline the importance of continual re‐appraisal of established long‐term climate data sets as new evidence becomes available. It is also likely that the identified biases in winter EWP have distorted many other long‐term European precipitation series.

Sex identification from distinctive gene expression patterns in Antarctic krill (Euphausia superba) - Leonie Suter; Andrea Maree Polanowski; Robert King; Chiara Romualdi; Gabriele Sales; So Kawaguchi; Simon Neil Jarman; Bruce Emerson Deagle (Polar Biology, 2019)
Antarctic krill ( Euphausia superba ) is a highly abundant keystone species of the Southern Ocean ecosystem, directly connecting primary producers to high-trophic level predators. Sex ratios of krill vary remarkably between swarms and this phenomenon is poorly understood, as identification of krill sex relies on external morphological differences that appear late during development. Sex determination mechanisms in krill are unknown, but could include genetic, environmental or parasitic mechanisms. Similarly, virtually nothing is known about molecular sex differentiation. The krill genome has to date not been sequenced, and due to its enormous size and large amount of repetitive elements, it is currently not feasible to develop sex-specific DNA markers. To produce a reliable molecular marker for sex in krill and to investigate molecular sex differentiation we therefore focused on identifying sex-specific transcriptomic differences. Through transcriptomic analysis, we found large gene expression differences between testes and ovaries and identified three genes exclusively expressed in female whole krill from early juvenile stages onwards. The sex-specific expression of these three genes persisted through sexual regression, although our regressed samples originated from a krill aquarium and may differ from wild-regressed krill. Two slightly male-biased genes did not display sufficient expression differences to clearly differentiate sexes. Based on the expression of the three female-specific genes we developed a molecular test that for the first time allows the unambiguous sex determination of krill samples lacking external sex-specific features from juvenile stages onwards, including the sexually regressed krill we examined.

Drivers of increased soil erosion in East Africa’s agro-pastoral systems: changing interactions between the social, economic and natural domains - Maarten Wynants; Claire Kelly; Kelvin Mtei; Linus Munishi; Aloyce Patrick; Anna Rabinovich; Mona Nasseri; David Gilvear; Neil Roberts; Pascal Boeckx; Geoff Wilson; William H. Blake; et al. (Regional Environmental Change, 2019)

Correction to: Adverse drug reaction causality assessment tools for drug-induced Stevens-Johnson syndrome and toxic epidermal necrolysis: room for improvement - Jennifer L. Goldman; Wen-Hung Chung; Brian R. Lee; Chun-Bing Chen; Chun-Wei Lu; Wolfram Hoetzenecker; Robert Micheletti; Sally Usdin Yasuda; David J. Margolis; Neil H. Shear; Jeffery P. Struewing; Munir Pirmohamed (European Journal of Clinical Pharmacology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Adverse drug reaction causality assessment tools for drug-induced Stevens-Johnson syndrome and toxic epidermal necrolysis: room for improvement - Jennifer L. Goldman; Wen-Hung Chung; Brian R. Lee; Chun-Bing Chen; Chun-Wei Lu; Wolfram Hoetzenecker; Robert Micheletti; Sally Usdin Yasuda; David J. Margolis; Neil H. Shear; Jeffery P Struewing; Munir Pirmohamed (European Journal of Clinical Pharmacology, 2019)

Rapid mapping of the spatial and temporal intensity of influenza - David J. Muscatello; Robert Neil F. Leong; Robin M. Turner; Anthony T. Newall (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Syntrophus aciditrophicus uses the same enzymes in a reversible manner to degrade and synthesize aromatic and alicyclic acids - Kimberly L. James; Johannes W. Kung; Bryan R. Crable; Housna Mouttaki; Jessica R. Sieber; Hong H. Nguyen; Yanan Yang; Yongming Xie; Jonathan Erde; Neil Q. Wofford; Elizabeth A. Karr; Joseph A. Loo; et al. (Environmental Microbiology, 2019)
Summary Syntrophy is essential for the efficient conversion of organic carbon to methane in natural and constructed environments, but little is known about the enzymes involved in syntrophic carbon and electron flow. Syntrophus aciditrophicus strain SB syntrophically degrades benzoate and cyclohexane‐1‐carboxylate and catalyses the novel synthesis of benzoate and cyclohexane‐1‐carboxylate from crotonate. We used proteomic, biochemical and metabolomic approaches to determine what enzymes are used for fatty, aromatic and alicyclic acid degradation versus for benzoate and cyclohexane‐1‐carboxylate synthesis. Enzymes involved in the metabolism of cyclohex‐1,5‐diene carboxyl‐CoA to acetyl‐CoA were in high abundance in S. aciditrophicus cells grown in pure culture on crotonate and in coculture with Methanospirillum hungatei on crotonate, benzoate or cyclohexane‐1‐carboxylate. Incorporation of 13 C‐atoms from 1‐[ 13 C]‐acetate into crotonate, benzoate and cyclohexane‐1‐carboxylate during growth on these different substrates showed that the pathways are reversible. A protein conduit for syntrophic reverse electron transfer from acyl‐CoA intermediates to formate was detected. Ligases and membrane‐bound pyrophosphatases make pyrophosphate needed for the synthesis of ATP by an acetyl‐CoA synthetase. Syntrophus aciditrophicus , thus, uses a core set of enzymes that operates close to thermodynamic equilibrium to conserve energy in a novel and highly efficient manner.

Cerebral torque is human specific and unrelated to brain size - Li Xiang; Timothy Crow; Neil Roberts (Brain Structure and Function, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Germline CDH1 mutations are a significant contributor to the high frequency of early-onset diffuse gastric cancer cases in New Zealand Māori - Christopher Hakkaart; Lis Ellison-Loschmann; Robert Day; Andrew Sporle; Jonathan Koea; Pauline Harawira; Soo Cheng; Michelle Gray; Tracey Whaanga; Neil Pearce; Parry Guilford (Familial Cancer, 2019)

In Vivo Predictive Dissolution and Simulation Workshop Report: Facilitating the Development of Oral Drug Formulation and the Prediction of Oral Bioperformance - Yasuhiro Tsume; Sanjaykumar Patel; Nikoletta Fotaki; Christel Bergstrӧm; Gordon L. Amidon; James G. Brasseur; Deanna M. Mudie; Duxin Sun; Marival Bermejo; Ping Gao; Wei Zhu; David C. Sperry; et al. (The AAPS Journal, 2018)

Pan‐Mediterranean Holocene vegetation and land‐cover dynamics from synthesized pollen data - Jessie Woodbridge; Neil Roberts; Ralph Fyfe (Journal of Biogeography, 2018)
Aim The Mediterranean is characterized by diverse and spatially heterogeneous mosaic landscapes. Within this study, a cluster analysis‐based method is developed for the classification of Mediterranean vegetation types based on modern and fossil pollen datasets. The application of this approach to multiple pollen records spanning the Mediterranean region has allowed temporal variations in vegetation dynamics to be explored throughout the Holocene. We ask how far back stable baseline vegetation communities can be identified in the pollen record, and whether those types considered to be characteristic of the Mediterranean landscapes have been present in the past as well as at the present. Location The research location includes the land areas surrounding the Mediterranean Sea. The pollen sites are principally located in mainland Spain, southern France, Greece and Turkey, Italy, North Africa, the Levant, and some Mediterranean islands. Methods A total of 5,641 samples from 158 fossil pollen records (cores) and 1,799 modern pollen surface samples were harmonized taxonomically and pollen count data summed into 200‐year time windows on a common time‐scale from 11,000 bp to the present‐day. Cluster analysis and community classification were used to identify major vegetation types along with other approaches to explore patterns in ecological datasets, such as Simpson's diversity index and nonmetric multidimensional scaling. Results The pollen datasets were classified into 11 closed forest/woodland and five open or scrubland vegetation types. Closed vegetation clusters declined from the mid‐Holocene with a marked increase in open or human‐modified vegetation types since 3,500 bp and with an increasing rate of vegetation change and habitat diversity through time. Main conclusions The Mediterranean has been a dynamic landscape throughout the Holocene with frequent changes in land cover identified in the pollen datasets. The pollen‐inferred clusters reveal a wider range of Mediterranean vegetation types than identified in previous studies; for example, including both beech and alder woods. Evergreen Oleaceae‐dominated shrubland is much better represented in modern than in fossil samples while mesic forest was abundant in the past but is uncommon today.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

“Periderm Disorder Syndrome”: a New Name for the Syndrome Formerly Referred to as Pink Eye - Edward C. Lulai; Robert P. Sabba; Philip Nolte; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2018)

Biodegradation of pentafluorosulfanyl-substituted aminophenol in Pseudomonas spp. - Marta Saccomanno; Sabir Hussain; Neil K. O’Connor; Petr Beier; Mate Somlyay; Robert Konrat; Cormac D. Murphy (Biodegradation, 2018)

Trajectories of change in Mediterranean Holocene vegetation through classification of pollen data - Ralph M. Fyfe; Jessie Woodbridge; C. Neil Roberts (Vegetation History and Archaeobotany, 2018)

The use of historical environmental monitoring data to test predictions on cross-scale ecological responses to alterations in river flows - Matthew J. Colloff; Ian C. Overton; Brent L. Henderson; Jane Roberts; Julian R. W. Reid; Roderick L. Oliver; Anthony D. Arthur; Tanya M. Doody; Neil C. Sims; Qifeng Ye; Susan M. Cuddy (Aquatic Ecology, 2018)

Brain structural and functional asymmetry in human situs inversus totalis - Guy Vingerhoets; Xiang Li; Lewis Hou; Stephanie Bogaert; Helena Verhelst; Robin Gerrits; Roma Siugzdaite; Neil Roberts (Brain Structure and Function, 2018)

Developing an empirical approach to optimal camera-trap deployment at mammal resting sites: evidence from a longitudinal study of an otter Lutra lutra holt - Melanie A. Findlay; Robert A. Briers; Neil Diamond; Patrick J. C. White (European Journal of Wildlife Research, 2017)

Infection by Uromyces euphorbiae: a trigger for the sporulation of endophytic Colletotrichum truncatum on the common host Euphorbia hirta - Érica Santos do Carmo de Souza; Helson Mario Martins do Vale; Rita de Cássia Pereira Carvalho; William Rosa de Oliveira Soares; Robert Neil Gerard Miller; José Carmine Dianese (Mycological Progress, 2017)

A climate stress test of Los Angeles’ water quality plans - Abdul Tariq; Robert Jay Lempert; John Riverson; Marla Schwartz; Neil Berg (Climatic Change, 2017)

Modeling of free fatty acid dynamics: insulin and nicotinic acid resistance under acute and chronic treatments - Robert Andersson; Tobias Kroon; Joachim Almquist; Mats Jirstrand; Nicholas D. Oakes; Neil D. Evans; Michael J. Chappel; Johan Gabrielsson (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Productivity and Connectivity in Tropical Riverscapes of Northern Australia: Ecological Insights for Management - Neil E. Pettit; Robert J. Naiman; Danielle M. Warfe; Tim D. Jardine; Michael M. Douglas; Stuart E. Bunn; Peter M. Davies (Ecosystems, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Vertex- and atlas-based comparisons in measures of cortical thickness, gyrification and white matter volume between humans and chimpanzees - William D. Hopkins; Xiang Li; Tim Crow; Neil Roberts (Brain Structure and Function, 2017)

Mechanistic evaluation of primary human hepatocyte culture using global proteomic analysis reveals a selective dedifferentiation profile - James A. Heslop; Cliff Rowe; Joanne Walsh; Rowena Sison-Young; Roz Jenkins; Laleh Kamalian; Richard Kia; David Hay; Robert P. Jones; Hassan Z. Malik; Stephen Fenwick; Amy E. Chadwick; et al. (Archives of Toxicology, 2017)

Urban forest structure, ecosystem services and change in Syracuse, NY - David J. Nowak; Robert E. Hoehn; Allison R. Bodine; Eric J. Greenfield; Jarlath O’Neil-Dunne (Urban Ecosystems, 2016)

Projected impacts of 21st century climate change on diapause in Calanus finmarchicus - Robert J. Wilson; Neil S. Banas; Michael R. Heath; Douglas C. Speirs (Global Change Biology, 2016)
Diapause plays a key role in the life cycle of high latitude zooplankton. During diapause, animals avoid starving in winter by living in deep waters where metabolism is lower and met by lipid reserves. Global warming is therefore expected to shorten the maximum potential diapause duration by increasing metabolic rates and by reducing body size and lipid reserves. This will alter the phenology of zooplankton, impact higher trophic levels and disrupt biological carbon pumps. Here, we project the impacts of climate change on the key North Atlantic copepod Calanus finmarchicus under IPCC RCP 8.5. Potential diapause duration is modelled in relation to body size and overwintering temperature. The projections show pronounced geographic variations. Potential diapause duration reduces by more than 30% in the Western Atlantic, whereas in the key overwintering centre of the Norwegian Sea it changes only marginally. Surface temperature rises, which reduce body size and lipid reserves, will have a similar impact to deep‐water changes on diapause in many regions. Because deep‐water warming lags that at the surface, animals in the Labrador Sea could offset warming impacts by diapausing in deeper waters. However, the ability to control diapause depth may be limited.

Carbon Flux and Carbohydrate Gene Families in Pineapple - Robert E. Paull; Nancy Jung Chen; Ray Ming; Ching Man Wai; Neil Shirley; Julian Schwerdt; Vincent Bulone (Tropical Plant Biology, 2016)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

Evolution of Mid-Atlantic Coastal and Back-Barrier Estuary Environments in Response to a Hurricane: Implications for Barrier-Estuary Connectivity - Jennifer L. Miselis; Brian D. Andrews; Robert S. Nicholson; Zafer Defne; Neil K. Ganju; Anthony Navoy (Estuaries and Coasts, 2016)

Exosomes derived from endometriotic stromal cells have enhanced angiogenic effects in vitro - Djana Harp; Adel Driss; Sharifeh Mehrabi; Indrajit Chowdhury; Wei Xu; Dong Liu; Minerva Garcia-Barrio; Robert N. Taylor; Bert Gold; Samantha Jefferson; Neil Sidell; Winston Thompson (Cell and Tissue Research, 2016)

Genetic isolation between coastal and fishery‐impacted, offshore bottlenose dolphin ( Tursiops spp.) populations - Simon J. Allen; Kate A. Bryant; Robert H. S. Kraus; Neil R. Loneragan; Anna M. Kopps; Alexander M. Brown; Livia Gerber; Michael Krützen (Molecular Ecology, 2016)
The identification of species and population boundaries is important in both evolutionary and conservation biology. In recent years, new population genetic and computational methods for estimating population parameters and testing hypotheses in a quantitative manner have emerged. Using a Bayesian framework and a quantitative model‐testing approach, we evaluated the species status and genetic connectedness of bottlenose dolphin ( Tursiops spp.) populations off remote northwestern Australia, with a focus on pelagic ‘offshore’ dolphins subject to incidental capture in a trawl fishery. We analysed 71 dolphin samples from three sites beyond the 50 m depth contour (the inshore boundary of the fishery) and up to 170 km offshore, including incidentally caught and free‐ranging individuals associating with trawl vessels, and 273 dolphins sampled at 12 coastal sites inshore of the 50 m depth contour and within 10 km of the coast. Results from 19 nuclear microsatellite markers showed significant population structure between dolphins from within the fishery and coastal sites, but also among dolphins from coastal sites, identifying three coastal populations. Moreover, we found no current or historic gene flow into the offshore population in the region of the fishery, indicating a complete lack of recruitment from coastal sites. Mitochondrial DNA corroborated our findings of genetic isolation between dolphins from the offshore population and coastal sites. Most offshore individuals formed a monophyletic clade with common bottlenose dolphins ( T. truncatus ), while all 273 individuals sampled coastally formed a well‐supported clade of Indo‐Pacific bottlenose dolphins ( T. aduncus ). By including a quantitative modelling approach, our study explicitly took evolutionary processes into account for informing the conservation and management of protected species. As such, it may serve as a template for other, similarly inaccessible study populations.

Impoundment constraint of fish niche diversity in a temperate Australian river - Debashish Mazumder; Robert J. Williams; Li Wen; Neil Saintilan; Chris T. Walsh (Hydrobiologia, 2016)

A tale of two lakes: a multi‐proxy comparison of Lateglacial and Holocene environmental change in Cappadocia, Turkey - Neil Roberts; Samantha L. Allcock; Fabien Arnaud; Jonathan R. Dean; Warren J. Eastwood; Matthew D. Jones; Melanie J. Leng; Sarah E. Metcalfe; Emmanuel Malet; Jessie Woodbridge; Hakan Yiğitbaşıoğlu (Journal of Quaternary Science, 2016)
Individual palaeoenvironmental records represent a combination of regional‐scale (e.g. climatic) and site‐specific local factors. Here we compare multiple climate proxies from two nearby maar lake records, assuming that common signals are due to regional‐scale forcing. A new core sequence from Nar Lake in Turkey is dated by varves and U–Th to the last 13.8 ka. Markedly dry periods during the Lateglacial stadial, at 4.3–3.7 and at 3.2–2.6 ka BP, are associated with peaks in Mg/dolomite, positive δ 18 O, elevated diatom‐inferred electrical conductivity, an absence of laminated sediments and low Quercus /chenopod ratios. Wet phases occurred during the early–mid Holocene and 1.5–0.6 ka BP, characterized by negative δ 18 O, calcite precipitation, high Ca/Sr ratios, a high percentage of planktonic diatoms, laminated sediments and high Quercus /chenopod ratios. Comparison with the record from nearby Eski Acıgöl shows good overall correspondence for many proxies, especially for δ 18 O. Differences are related to basin infilling and lake ontogeny at Eski Acıgöl, which consequently fails to register climatic changes during the last 2 ka, and to increased flux of lithogenic elements into Nar Lake during the last 2.6 ka, not primarily climatic in origin. In attempting to separate a regional signal from site‐specific ‘noise’, two lakes may therefore be better than one.

Reinvigorating the scenario technique to expand uncertainty consideration - Evelina Trutnevyte; Céline Guivarch; Robert Lempert; Neil Strachan (Climatic Change, 2016)

Supramolecular organization of photosynthetic complexes in membranes of Roseiflexus castenholzii - Erica L.-W. Majumder; John D. Olsen; Pu Qian; Aaron M. Collins; C. Neil Hunter; Robert E. Blankenship (Photosynthesis Research, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Cellular therapy in combination with cytokines improves survival in a xenograft mouse model of ovarian cancer - Susan B. Ingersoll; Sarfraz Ahmad; Hasina C. McGann; Robert K. Banks; Nicole M. Stavitzski; Milan Srivastava; Ghazanfar Ali; Neil J. Finkler; John R. Edwards; Robert W. Holloway (Molecular and Cellular Biochemistry, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

From forest to farmland: pollen‐inferred land cover change across Europe using the pseudobiomization approach - Ralph M. Fyfe; Jessie Woodbridge; Neil Roberts (Global Change Biology, 2015)
Maps of continental‐scale land cover are utilized by a range of diverse users but whilst a range of products exist that describe present and recent land cover in Europe, there are currently no datasets that describe past variations over long time‐scales. User groups with an interest in past land cover include the climate modelling community, socio‐ecological historians and earth system scientists. Europe is one of the continents with the longest histories of land conversion from forest to farmland, thus understanding land cover change in this area is globally significant. This study applies the pseudobiomization method ( PBM ) to 982 pollen records from across Europe, taken from the European Pollen Database ( EPD ) to produce a first synthesis of pan‐European land cover change for the period 9000 bp to present, in contiguous 200 year time intervals. The PBM transforms pollen proportions from each site to one of eight land cover classes ( LCC s) that are directly comparable to the CORINE land cover classification. The proportion of LCC s represented in each time window provides a spatially aggregated record of land cover change for temperate and northern Europe, and for a series of case study regions (western France, the western Alps, and the Czech Republic and Slovakia). At the European scale, the impact of Neolithic food producing economies appear to be detectable from 6000 bp through reduction in broad‐leaf forests resulting from human land use activities such as forest clearance. Total forest cover at a pan‐European scale moved outside the range of previous background variability from 4000 bp onwards. From 2200 bp land cover change intensified, and the broad pattern of land cover for preindustrial Europe was established by 1000 bp . Recognizing the timing of anthropogenic land cover change in Europe will further the understanding of land cover‐climate interactions, and the origins of the modern cultural landscape.

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

A comparison of remotely sensed and pollen‐based approaches to mapping Europe's land cover - Jessie Woodbridge; Ralph M. Fyfe; Neil Roberts (Journal of Biogeography, 2014)
Aim Remote sensing coupled with direct observation allows recent changes in vegetation to be investigated but, in order to extend our understanding of land‐cover change further back in time, different proxies for vegetation are required. The pseudobiomization ( PBM ) approach has been developed to transform fossil pollen data into land‐cover classes ( LCC s) in order to reconstruct broad‐scale anthropogenic land‐use change through time. The aim of this study was to test and refine the PBM approach through application to an extensive modern pollen dataset and comparison with remotely sensed CORINE land‐cover maps for Europe. Location The study area comprised 2471 modern pollen sites from across Europe. Methods Pollen sites were assigned to one of eight LCC s using the pollen‐based PBM method, which draws upon biomization techniques to transform pollen data into records of land‐cover change. Five of the LCC s were ‘pure’ classes (e.g. broad‐leaf forest) and three of them were mixed vegetation. Remotely sensed CORINE land‐cover maps were used to assign LCC s to sites, and the results were compared with pollen‐assigned LCC s. Results The results revealed a good correspondence between the proportions of different LCC s that were registered using CORINE and pollen‐based PBM , when data were aggregated at a pan‐European scale. However, the match between the two datasets was much less close at a site‐specific level. The overall results were improved to c. 60% when the target was broadened to include similar as well as identical LCC s. The spatial correspondence was best across north‐central Europe and least good in south‐west Europe, the Mediterranean and northern Scandinavia. Main conclusions The ability of distinct data types to sense actual vegetation is limited by various sources of error; for example, both pollen and remote sensing vary in terms of spatial and temporal heterogeneity and taxonomic resolution. It is likely that many of the main sources of error are common to both methods, rather than being approach‐specific. We conclude that pollen‐based methods of intermediate complexity can be used as a proxy for broad‐scale land‐cover change across most of temperate Europe, but may be less reliable at a site‐specific scale.

Mercury Accumulation in Sharks From the Coastal Waters of Southwest Florida - Darren Rumbold; Robert Wasno; Neil Hammerschlag; Aswani Volety (Archives of Environmental Contamination and Toxicology, 2014)

Dissolved organic carbon biolability decreases along with its modernization in fluvial networks in an ancient landscape - Jason B. Fellman; Robert G. M. Spencer; Peter A. Raymond; Neil E. Pettit; Grzegorz Skrzypek; Peter J. Hernes; Pauline F. Grierson (Ecology, 2014)
The metabolism of dissolved organic carbon (DOC) along fluvial networks determines what fraction of organic matter is exported to the ocean. Although it is thought fresh rather than older DOC is preferred by bacteria, old DOC can also be highly bioavailable to stream bacterial communities. In strongly seasonal and oligotrophic regions, we argue that groundwater inputs of old DOC may increase the bioavailability of stream organic matter. We sampled 22 streams along a gradient of size (wetted widths from 1 to 60 m) and one groundwater spring in the Kimberley region of northwest Australia to determine how the age and bioavailability of streamwater DOC varied with stream size. Our hypothesis was that stream DOC would become more enriched in 14 C (younger) and less bioavailable as streams increased in size and depleted 14 C‐DOC was metabolized by stream microbial communities. We also used fluorescence characterization of DOC, ultraviolet absorbance at 254nm (SUVA 254 ), δ 13 C‐DOC and lignin phenol yields to assess how these indicators of DOC character influenced the bioavailability and age of stream DOC. Stream evaporation/inflow ratios ( E / I , used as a proxy for catchment water residence time), determined from changes in stream δ 18 O along the gradient of stream size, were positively related to DOC concentration and carbon‐normalized lignin yields, while δ 13 C‐DOC became more depleted with increasing E / I . Stream Δ 14 C‐DOC varied from −452.1‰ (groundwater) to 48.9‰ and showed progressive enrichment as streams increased in size and accumulated DOC mainly from terrestrial plant material. Older DOC corresponded to higher bioavailability ( R 2 = 0.67, P 14 C‐depleted carbon, is common to one of the oldest landscapes on earth. Therefore, rapid biotic uptake of old bioavailable DOC originating in groundwater springs and the accumulation of modern, terrestrially derived DOC work in opposite directions affecting DOC dynamics along fluvial networks. We suggest the metabolism of old DOC along fluvial networks provides a biogeochemical link between non‐contemporary carbon fixation and modern river productivity.

From Bench to Humans: Formulation Development of a Poorly Water Soluble Drug to Mitigate Food Effect - Preetanshu Pandey; Rhye Hamey; Dilbir S. Bindra; Zongyun Huang; Neil Mathias; Timothy Eley; John Crison; Brian Yan; Robert Perrone; Chandra Vemavarapu (AAPS PharmSciTech, 2014)

Exchange of Nitrogen and Phosphorus Between a Shallow Lagoon and Coastal Waters - Melanie Hayn; Robert Howarth; Roxanne Marino; Neil Ganju; Peter Berg; Kenneth H. Foreman; Anne E. Giblin; Karen McGlathery (Estuaries and Coasts, 2014)

Assessment of extracellular dehydration using saliva osmolality - Brett R. Ely; Samuel N. Cheuvront; Robert W. Kenefick; Marissa G. Spitz; Kristen R. Heavens; Neil P. Walsh; Michael N. Sawka (European Journal of Applied Physiology, 2014)

A new method for producing transgenic birds via direct in vivo transfection of primordial germ cells - Scott G. Tyack; Kristie A. Jenkins; Terri E. O’Neil; Terry G. Wise; Kirsten R. Morris; Matthew P. Bruce; Scott McLeod; Alexander J. Wade; James McKay; Robert J. Moore; Karel A. Schat; John W. Lowenthal; et al. (Transgenic Research, 2013)

Age-Related Task Sensitivity of Frontal EEG Entropy During Encoding Predicts Retrieval - Denis O’Hora; Stefan Schinkel; Michael J. Hogan; Liam Kilmartin; Michael Keane; Robert Lai; Neil Upton (Brain Topography, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Soil biotransformation of thiodiglycol, the hydrolysis product of mustard gas: understanding the factors governing remediation of mustard gas contaminated soil - Hong Li; Robert Muir; Neil R. McFarlane; Richard J. Soilleux; Xiaohong Yu; Ian P. Thompson; Simon A. Jackman (Biodegradation, 2013)

Expression of stromal genes associated with the angiogenic response are not differentiated between human tumour xenografts with divergent vascular morphologies - Matthew Farren; Susie Weston; Helen Brown; Nicola Broadbent; Steve Powell; Robert Shaw; Neil R. Smith; Rachael Inglis; Alex Graham; Sue Ashton; Stephen R. Wedge; Simon T. Barry (Angiogenesis, 2012)

Climate Change and Population Growth in Timor Leste: Implications for Food Security - Nicholas Molyneux; Gil Rangel da Cruz; Robert L. Williams; Rebecca Andersen; Neil C. Turner (Ambio, 2012)

Multiproxy record for the last 4500 years from Lake Shkodra (Albania/Montenegro) - Giovanni Zanchetta; Aurelien Van Welden; Ilaria Baneschi; Russell Drysdale; Laura Sadori; Neil Roberts; Marco Giardini; Christian Beck; Vincenzo Pascucci; Roberto Sulpizio (Journal of Quaternary Science, 2012)
A multi‐proxy record is presented for approximately the last 4500 cal a BP from Lake Shkodra, Albania/Montenegro. Lithological analyses, C/N ratio and δ 13 C of the organic and inorganic carbon component suggest that organic matter and bulk carbonate are predominantly authigenic. The δ 18 O record of bulk carbonate indicates the presence of two prominent wet periods: one at ca. 4300 cal a BP and one at ca. 2500–2000 cal a BP. The latter phase is also found in southern Spain and Central Italy, and represents a prominent event in the western and central Mediterranean. In the last 2000 years, four relatively wet intervals occurred between ca. 1800 and 1500 cal a BP (150–450 AD), 1350–1250 (600–700 AD), 1100–800 (850–1150 AD), and at ca. 90 cal a BP (1860 AD). Between ca. 4100 and 2500 cal a BP δ 18 O values are relatively high, with three prominent peaks indicating drier conditions at ca. 4100–4000 cal a BP, ca. 3500 and at ca. 3300 cal a BP. Four additional drier events are identified at 1850 (ca. 100 AD), 1400 (ca. 550 AD), 1150 (800 AD) and ca.750 cal a BP (1200 AD). The pollen record does not show changes in accordance with these episodes owing to the poor sensitivity of vegetation in this area, which is dominated by an orographic rainfall effect and where changes in altitudinal vegetation belts do not affect the pollen rain in the lake catchment. However, since ca. 900 cal a BP a significant decrease in the percentage arboreal pollen and in pollen concentrations suggest major deforestation produced by human activities. Copyright © 2012 John Wiley & Sons, Ltd.

A physiological trait‐based approach to predicting the responses of species to experimental climate warming - Sarah E. Diamond; Lauren M. Nichols; Neil McCoy; Christopher Hirsch; Shannon L. Pelini; Nathan J. Sanders; Aaron M. Ellison; Nicholas J. Gotelli; Robert R. Dunn (Ecology, 2012)
Physiological tolerance of environmental conditions can influence species‐level responses to climate change. Here, we used species‐specific thermal tolerances to predict the community responses of ant species to experimental forest‐floor warming at the northern and southern boundaries of temperate hardwood forests in eastern North America. We then compared the predictive ability of thermal tolerance vs. correlative species distribution models (SDMs) which are popular forecasting tools for modeling the effects of climate change. Thermal tolerances predicted the responses of 19 ant species to experimental climate warming at the southern site, where environmental conditions are relatively close to the ants' upper thermal limits. In contrast, thermal tolerances did not predict the responses of the six species in the northern site, where environmental conditions are relatively far from the ants' upper thermal limits. Correlative SDMs were not predictive at either site. Our results suggest that, in environments close to a species' physiological limits, physiological trait‐based measurements can successfully forecast the responses of species to future conditions. Although correlative SDMs may predict large‐scale responses, such models may not be accurate for predicting site‐level responses.

Tidal and Groundwater Fluxes to a Shallow, Microtidal Estuary: Constraining Inputs Through Field Observations and Hydrodynamic Modeling - Neil K. Ganju; Melanie Hayn; Shih-Nan Chen; Robert W. Howarth; Patrick J. Dickhudt; Alfredo L. Aretxabaleta; Roxanne Marino (Estuaries and Coasts, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Sources of groundwater pumpage in a layered aquifer system in the Upper Gulf Coastal Plain, USA - Yun Huang; Bridget R. Scanlon; Jean-Philippe Nicot; Robert C. Reedy; Alan R. Dutton; Van A. Kelley; Neil E. Deeds (Hydrogeology Journal, 2012)

Effect of daily mixed nutritional supplementation on immune indices in soldiers undertaking an 8-week arduous training programme - Bethany C. Diment; Matthew B. Fortes; Julie P. Greeves; Anna Casey; Ricardo J. S. Costa; Robert Walters; Neil P. Walsh (European Journal of Applied Physiology, 2012)

‘Null Method’ Determination of Drug Biophase Concentration - Ronald J. Tallarida; Neil Lamarre; Robert B. Raffa (Pharmaceutical Research, 2012)

Behavioural and electrophysiological effects of visual paired associate context manipulations during encoding and recognition in younger adults, older adults and older cognitively declined adults - Michael J. Hogan; Joanne P. M. Kenney; Richard A. P. Roche; Michael A. Keane; Jennifer L. Moore; Jochen Kaiser; Robert Lai; Neil Upton (Experimental Brain Research, 2012)

A specialist root herbivore exploits defensive metabolites to locate nutritious tissues - Christelle A. M. Robert; Nathalie Veyrat; Gaétan Glauser; Guillaume Marti; Gwladys R. Doyen; Neil Villard; Mickaël D. P. Gaillard; Tobias G. Köllner; David Giron; Mélanie Body; Benjamin A. Babst; Richard A. Ferrieri; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 55–64 Abstract The most valuable organs of plants are often particularly rich in essential elements, but also very well defended. This creates a dilemma for herbivores that need to maximise energy intake while minimising intoxication. We investigated how the specialist root herbivore Diabrotica virgifera solves this conundrum when feeding on wild and cultivated maize plants. We found that crown roots of maize seedlings were vital for plant development and, in accordance, were rich in nutritious primary metabolites and contained higher amounts of the insecticidal 2,4‐dihydroxy‐7‐methoxy‐1,4‐benzoxazin‐3‐one (DIMBOA) and the phenolic compound chlorogenic acid. The generalist herbivores Diabrotica balteata and Spodoptera littoralis were deterred from feeding on crown roots, whereas the specialist D. virgifera preferred and grew best on these tissues. Using a 1,4‐benzoxazin‐3‐one‐deficient maize mutant, we found that D. virgifera is resistant to DIMBOA and other 1,4‐benzoxazin‐3‐ones and that it even hijacks these compounds to optimally forage for nutritious roots.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Effects of a nonnative, invasive lovegrass on Agave palmeri distribution, abundance, and insect pollinator communities - Denise L. Lindsay; Pamela Bailey; Richard F. Lance; Michael J. Clifford; Robert Delph; Neil S. Cobb (Biodiversity and Conservation, 2011)

Neurometabolite Abnormalities in Simian Immunodeficiency Virus-Infected Macaques with Chronic Morphine Administration - Christine C. Cloak; Linda Chang; Shawn P. O’Neil; Thomas M. Ernst; Daniel C. Anderson; Robert M. Donahoe (Journal of Neuroimmune Pharmacology, 2011)

Candida northwykensis sp. nov., A Novel Yeast Isolated from the Gut of the Click Beetle Melanotus villosus - Sreenivas Rao Ravella; Neil Donovan; Stephen A. James; Sisinthy Shivaji; Kotakonda Arunasri; Christopher J. Bond; Ian N. Roberts; Phil J. Hobbs (Current Microbiology, 2011)

Electroencephalographic coherence, aging, and memory: distinct responses to background context and stimulus repetition in younger, older, and older declined groups - Michael Hogan; Peter Collins; Michael Keane; Liam Kilmartin; Jochen Kaiser; Joanne Kenney; Robert Lai; Neil Upton (Experimental Brain Research, 2011)

Linking neo- and palaeolimnology: a case study using crater lake diatoms from central Turkey - Jessie Woodbridge; Neil Roberts (Journal of Paleolimnology, 2010)

Passive Treatment of Acidic Coal Mine Drainage: The Anna S Mine Passive Treatment Complex - Robert Hedin; Ted Weaver; Neil Wolfe; Kimberly Weaver (Mine Water and the Environment, 2010)

Neurological suppression of diaphragm electromyographs in hamsters infected with West Nile virus - John D Morrey; Venkatraman Siddharthan; Hong Wang; Jeffery O Hall; Neil E Motter; Robert D Skinner; Ramona T Skirpstunas (Journal of NeuroVirology, 2010)

Intraspecific Geographic Variation of Fragrances Acquired by Orchid Bees in Native and Introduced Populations - Santiago R. Ramírez; Thomas Eltz; Falko Fritzsch; Robert Pemberton; Elizabeth G. Pringle; Neil D. Tsutsui (Journal of Chemical Ecology, 2010)

Nitrogen in Runoff from Residential Roads in a Coastal Area - Eric A. Davidson; Kathleen E. Savage; Neil D. Bettez; Roxanne Marino; Robert W. Howarth (Water, Air, & Soil Pollution, 2010)

Deciphering the Chemical Basis of Nestmate Recognition - Ellen van Wilgenburg; Robert Sulc; Kenneth J. Shea; Neil D. Tsutsui (Journal of Chemical Ecology, 2010)

The effects of two nights of sleep deprivation with or without energy restriction on immune indices at rest and in response to cold exposure - Ricardo J. S. Costa; Adam Harper Smith; Samuel J. Oliver; Robert Walters; Norbert Maassen; James L. J. Bilzon; Neil Peter Walsh (European Journal of Applied Physiology, 2010)

Social and ecological facets of pest management in Honduran subsistence agriculture: implications for IPM extension and natural resource management - Kris A. G. Wyckhuys; Robert J. O’Neil (Environment, Development and Sustainability, 2010)

The influence of defined ante-mortem stressors on the early post-mortem biochemical processes in the abdominal muscle of the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) - Sebastian G. Gornik; Amaya Albalat; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2010)

Fire, climate and the origins of agriculture: micro‐charcoal records of biomass burning during the last glacial–interglacial transition in Southwest Asia - Rebecca Turner; Neil Roberts; Warren J. Eastwood; Emma Jenkins; Arlene Rosen (Journal of Quaternary Science, 2010)
This study investigates changes in climate, vegetation, wildfire and human activity in Southwest Asia during the transition to Neolithic agriculture between ca. 16 and ca. 9 ka. In order to trace the fire history of this region, we use microscopic charcoal from lake sediment sequences, and present two new records: one from south central Turkey (Akgöl) and the other from the southern Levant (Hula). These are interpreted primarily as the result of regional‐scale fire events, with the exception of a single large event ca. 13 ka at Akgöl, which phytolith analysis shows was the result of burning of the local marsh vegetation. Comparison between these and other regional micro‐charcoal, stable isotope and pollen records shows that wildfires were least frequent when the climate was cold and dry (glacial, Lateglacial Stadial) and the vegetation dominated by chenopod– Artemisia steppe, and that they became more frequent and/or bigger at times of warmer, wetter but seasonally dry climate (Lateglacial Interstadial, early Holocene). Warmer and wetter climates caused an increase in biomass availability, with woody matter appearing to provide the main fuel source in sites from the Levant, while grass fires predominated in the interior uplands of Anatolia. Southwest Asia's grasslands reached their greatest extent during the early Holocene, and they were maintained by dry‐season burning that helped to delay the spread of woodland by up to 3 ka, at the same time as Neolithic settlement became established across this grass parkland landscape. Although climatic changes appear to have acted as the principal ‘pacemaker’ for fire activity through the last glacial–interglacial climatic transition (LGIT), human actions may have amplified shifts in biomass burning. Fire regimes therefore changed markedly during this time period, and both influenced, and were influenced by, the cultural‐economic transition from hunter‐foraging to agriculture and village life. Copyright © 2009 John Wiley & Sons, Ltd.

Incidence of endornaviruses in Phytophthora taxon douglasfir and Phytophthora ramorum - Zisis Kozlakidis; Neil A. Brown; Atif Jamal; Xiyu Phoon; Robert H. A. Coutts (Virus Genes, 2010)

Retrospective assessment of dryland soil stability in relation to grazing and climate change - Robert A. Washington-Allen; Neil E. West; R. Douglas Ramsey; Debra H. Phillips; Herman H. Shugart (Environmental Monitoring and Assessment, 2010)

Wolverine gene flow across a narrow climatic niche - Michael K. Schwartz; Jeffrey P. Copeland; Neil J. Anderson; John R. Squires; Robert M. Inman; Kevin S. McKelvey; Kristy L. Pilgrim; Lisette P. Waits; Samuel A. Cushman (Ecology, 2009)
Wolverines ( Gulo gulo ) are one of the rarest carnivores in the contiguous United States. Effective population sizes in Montana, Idaho, and Wyoming, where most of the wolverines in the contiguous United States exist, were calculated to be 35 (credible limits, 28–52) suggesting low abundance. Landscape features that influence wolverine population substructure and gene flow are largely unknown. Recent work has identified strong associations between areas with persistent spring snow and wolverine presence and range. We tested whether a dispersal model in which wolverines prefer to disperse through areas characterized by persistent spring snow cover produced least‐cost paths among all individuals that correlated with genetic distance among individuals. Models simulating large preferences for dispersing within areas characterized by persistent spring snow explained the data better than a model based on Euclidean distance. Partial Mantel tests separating Euclidean distance from spring snow‐cover‐based effects indicated that Euclidean distance was not significant in describing patterns of genetic distance. Because these models indicated that successful dispersal paths followed areas characterized by spring snow cover, we used these understandings to derive empirically based least‐cost corridor maps in the U.S. Rocky Mountains. These corridor maps largely explain previously published population subdivision patterns based on mitochondrial DNA and indicate that natural colonization of the southern Rocky Mountains by wolverines will be difficult but not impossible.

Effect of capture method on the physiology and nucleotide breakdown products in the Norway lobster ( Nephrops norvegicus ) - Amaya Albalat; Sebastian G. Gornik; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2009)

High-resolution array comparative genomic hybridization analysis reveals unanticipated complexity of genetic deficiencies on chromosome V in Caenorhabditis elegans - Martin R. Jones; Shu Yi Chua; Nigel J. O’Neil; Robert C. Johnsen; Ann M. Rose; David L. Baillie (Molecular Genetics and Genomics, 2009)

Zooplankton inputs and outputs in the saltmarsh at Towra Point, Australia - Debashish Mazumder; Neil Saintilan; Robert J. Williams (Wetlands Ecology and Management, 2009)

Reactions of hard red spring wheat to common root rot under field conditions of Northern United States of America - Dennis J. Tobias; Robert W. Stack; Krishna D. Puri; Neil Riveland; Shaobin Zhong (Euphytica, 2009)

Differential impact of adults and nymphs of a generalist predator on an exotic invasive pest demonstrated by molecular gut-content analysis - James D. Harwood; Ho Jung S. Yoo; Matthew H. Greenstone; Daniel L. Rowley; Robert J. O’Neil (Biological Invasions, 2009)

No effect of a 30-h period of sleep deprivation on leukocyte trafficking, neutrophil degranulation and saliva IgA responses to exercise - J. S. Costa Ricardo; Louise Cartner; Samuel J. Oliver; Stewart J. Laing; Robert Walters; James L. J. Bilzon; Neil P. Walsh (European Journal of Applied Physiology, 2009)

Evolution of West Rota Volcano, an extinct submarine volcano in the southern Mariana Arc: Evidence from sea floor morphology, remotely operated vehicle observations and 40 Ar– 39 Ar geochronological studies - Robert J. Stern; Yoshihiko Tamura; Robert W. Embley; Osamu Ishizuka; Susan G. Merle; Neil K. Basu; Hiroshi Kawabata; Sherman H. Bloomer (Island Arc, 2008)
West Rota Volcano (WRV) is a recently discovered extinct submarine volcano in the southern Mariana Arc. It is large (25 km diameter base), shallow (up to 300 m below sealevel), and contains a large caldera (6 × 10 km, with up to 1 km relief). The WRV lies near the northern termination of a major NNE‐trending normal fault. This and a second, parallel fault just west of the volcano separate uplifted, thick frontal arc crust to the east from subsiding, thin back‐arc basin crust to the west. The WRV is distinct from other Mariana Arc volcanoes: (i) it consists of a lower, predominantly andesite section overlain by a bimodal rhyolite‐basalt layered sequence; (ii) andesitic rocks are locally intensely altered and mineralized; (iii) it has a large caldera; and (iv) WRV is built on a major fault. Submarine felsic calderas are common in the Izu and Kermadec Arcs but are otherwise unknown from the Marianas and other primitive, intraoceanic arcs. 40 Ar– 39 Ar dating indicates that andesitic volcanism comprising the lower volcanic section occurred 0.33–0.55 my ago, whereas eruption of the upper rhyolites and basalts occurred 37–51 thousand years ago. Four sequences of rhyolite pyroclastics each are 20–75 m thick, unwelded and show reverse grading, indicating submarine eruption. The youngest unit consists of 1–2 m diameter spheroids of rhyolite pumice, interpreted as magmatic balloons, formed by relatively quiet effusion and inflation of rhyolite into the overlying seawater. Geochemical studies indicate that felsic magmas were generated by anatexis of amphibolite‐facies meta‐andesites, perhaps in the middle arc crust. The presence of a large felsic volcano and caldera in the southern Marianas might indicate interaction of large normal faults with a mid‐crustal magma body at depth, providing a way for viscous felsic melts to reach the surface.

Fire in the Riparian Zone: Characteristics and Ecological Consequences - Neil E. Pettit; Robert J. Naiman (Ecosystems, 2007)

Tracking the role of alternative prey in soybean aphid predation by Orius insidiosus : a molecular approach - JAMES D. HARWOOD; NICOLAS DESNEUX; HO JUNG S. YOO; DANIEL L. ROWLEY; MATTHEW H. GREENSTONE; JOHN J. OBRYCKI; ROBERT J. O′NEIL (Molecular Ecology, 2007)
The soybean aphid, Aphis glycines (Hemiptera: Aphididae), is a pest of soybeans in Asia, and in recent years has caused extensive damage to soybeans in North America. Within these agroecosystems, generalist predators form an important component of the assemblage of natural enemies, and can exert significant pressure on prey populations. These food webs are complex and molecular gut‐content analyses offer nondisruptive approaches for examining trophic linkages in the field. We describe the development of a molecular detection system to examine the feeding behaviour of Orius insidiosus (Hemiptera: Anthocoridae) upon soybean aphids, an alternative prey item, Neohydatothrips variabilis (Thysanoptera: Thripidae), and an intraguild prey species, Harmonia axyridis (Coleoptera: Coccinellidae). Specific primer pairs were designed to target prey and were used to examine key trophic connections within this soybean food web. In total, 32% of O. insidiosus were found to have preyed upon A. glycines , but disproportionately high consumption occurred early in the season, when aphid densities were low. The intensity of early season predation indicates that O. insidiosus are important biological control agents of A. glycines , although data suggest that N. variabilis constitute a significant proportion of the diet of these generalist predators. No Orius were found to contain DNA of H. axyridis , suggesting intraguild predation upon these important late‐season predators during 2005 was low. In their entirety, these results implicate O. insidiosus as a valuable natural enemy of A. glycines in this soybean agroecosystem.

Holocene climate change in the eastern Mediterranean region: a comparison of stable isotope and pollen data from Lake Gölhisar, southwest Turkey - Warren J. Eastwood; Melanie J. Leng; Neil Roberts; Basil Davis (Journal of Quaternary Science, 2007)
Stable isotope and pollen data from Gölhisar Gölü, a small intramontane lake located in southwest Turkey, provide complementary records of Holocene climate change. Modern oxygen and hydrogen isotope water data are used as a means of comparing present‐day isotope composition of the lake water to the past oxygen isotope composition of the lake water as calculated from 18 O/ 16 O ratios in calcite precipitated in the summer months. Despite the lake system being chemically dilute, the modern isotope data clearly establish that the lake water is evaporated in relation to its spring input, suggesting that the palaeo data can be interpreted primarily in terms of changing precipitation/evaporation ratios. δ 18 O and δ 13 C values from authigenic calcite through the Holocene show predominantly negative values indicating climatic conditions wetter than today. Particularly notable are low (depleted) isotope values during the earliest Holocene (ca. 10 600–8800 cal. yr. BP), a period for which pollen data imply drier conditions than at present. This divergence between pollen‐inferred and stable isotope palaeoclimate data is found in other east Mediterranean lake sediment records, and suggests that vegetation may have taken several millennia to reach climatic equilibrium at the start of the Holocene. Isotopic fluctuations during the early‐to‐mid Holocene (8800–5100 cal. yr. BP) suggest oscillations between aridity and humidity. Higher δ 18 O and δ 13 C values for the second half of the Holocene indicate generally drier conditions than during the period before ca.5100 cal. yr BP although there is some evidence for increased humidity coinciding with pollen evidence for increasing human impact and intensification of agriculture, notably during the so‐called Beyşehir Occupation Phase (Classical and early Byzantine periods). The modern trend towards aridity started about 1300 yr ago. Copyright © 2006 John Wiley & Sons, Ltd.

Differential immunogold localisation of sulphated and unsulphated keratan sulphate proteoglycans in normal and macular dystrophy cornea using sulphation motif-specific antibodies - Robert D. Young; Tomoya O. Akama; Petra Liskova; Neil D. Ebenezer; Bruce Allan; Briedgeen Kerr; Bruce Caterson; Michiko N. Fukuda; Andrew J. Quantock (Histochemistry and Cell Biology, 2006)

Impact of Criticism of Null‐Hypothesis Significance Testing on Statistical Reporting Practices in Conservation Biology - FIONA FIDLER; MARK A. BURGMAN; GEOFF CUMMING; ROBERT BUTTROSE; NEIL THOMASON (Conservation Biology, 2006)
Over the last decade, criticisms of null‐hypothesis significance testing have grown dramatically, and several alternative practices, such as confidence intervals, information theoretic, and Bayesian methods, have been advocated. Have these calls for change had an impact on the statistical reporting practices in conservation biology? In 2000 and 2001, 92% of sampled articles in Conservation Biology and Biological Conservation reported results of null‐hypothesis tests. In 2005 this figure dropped to 78%. There were corresponding increases in the use of confidence intervals, information theoretic, and Bayesian techniques. Of those articles reporting null‐hypothesis testing—which still easily constitute the majority—very few report statistical power (8%) and many misinterpret statistical nonsignificance as evidence for no effect (63%). Overall, results of our survey show some improvements in statistical practice, but further efforts are clearly required to move the discipline toward improved practices.

Fish Assemblages in Three Tidal Saltmarsh and Mangrove Flats in Temperate NSW, Australia: A Comparison Based on Species Diversity and Abundance - Debashish Mazumder; Neil Saintilan; Robert J. Williams (Wetlands Ecology and Management, 2006)

Molecular genotype identification of the Gallus gallus major histocompatibility complex - Janet E. Fulton; Helle R. Juul-Madsen; Christopher M. Ashwell; Amy M. McCarron; James A. Arthur; Neil P. O’Sullivan; Robert L. Taylor (Immunogenetics, 2006)

A Coupled Calibration and Modelling Approach to the Understanding of Dry-Land Lake Oxygen Isotope Records - Matthew D. Jones; Melanie J. Leng; C. Neil Roberts; Murat Türkeş; Rana Moyeed (Journal of Paleolimnology, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Flood-deposited wood debris and its contribution to heterogeneity and regeneration in a semi-arid riparian landscape - Neil E. Pettit; Robert J. Naiman (Oecologia, 2005)

Temporal Variations in Fish Catch Using Pop Nets in Mangrove and Saltmarsh Flats at Towra Point, NSW, Australia - Debashish Mazumder; Neil Saintilan; Robert J. Williams (Wetlands Ecology and Management, 2005)

Patterns and Interpretation of Mercury Exposure in Freshwater Avian Communities in Northeastern North America - David C. Evers; Neil M. Burgess; Louise Champoux; Bart Hoskins; Andrew Major; Wing M. Goodale; Robert J. Taylor; Robert Poppenga; Theresa Daigle (Ecotoxicology, 2005)

Mercury in Freshwater Fish of Northeast North America ? A Geographic Perspective Based on Fish Tissue Monitoring Databases - Neil C Kamman; Neil M. Burgess; Charles T. Driscoll; Howard A. Simonin; Wing Goodale; Janice Linehan; Robert Estabrook; Michael Hutcheson; Andrew Major; Anton M. Scheuhammer; David A. Scruton (Ecotoxicology, 2005)

Uncertainties due to transport-parameter sensitivity in an efficient 3-D ocean-climate model - Neil R. Edwards; Robert Marsh (Climate Dynamics, 2005)

Sequence and expression of C-type lectin receptors in Atlantic salmon (Salmo salar) - Kelly H. Soanes; Kevin Figuereido; Robert C. Richards; Neil R. Mattatall; K. Vanya Ewart (Immunogenetics, 2004)

Global change in the Holocene - Neil Roberts (Journal of Paleolimnology, 2004)

Serpins in Unicellular Eukarya, Archaea, and Bacteria: Sequence Analysis and Evolution - Thomas H. Roberts; Jrn Hejgaard; Neil F. W. Saunders; Ricardo Cavicchioli; Paul M. G. Curmi (Journal of Molecular Evolution, 2004)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

The Vulnerability of the Australian Beef Industry to Impacts of the Cattle Tick (Boophilus microplus) under Climate Change - Neil White; Robert W. Sutherst; Nigel Hall; Patrick Whish-Wilson (Climatic Change, 2003)

Environmental change: more than just another encyclopaedic dictionary - Neil Roberts (Journal of Biogeography, 2003)

Above‐ and below‐ground responses of C 3 –C 4 species mixtures to elevated CO 2 and soil water availability - JUSTIN D. DERNER; HYRUM B. JOHNSON; BRUCE A. KIMBALL; PAUL J. PINTER; H. Wayne POLLEY; CHARLES R. TISCHLER; THOMAS W. BOUTTON; ROBERT L. LAMORTE; GERALD W. WALL; NEIL R. ADAM; STEVEN W. LEAVITT; MICHAEL J. OTTMAN; et al. (Global Change Biology, 2003)
We evaluated the influences of CO 2 [Control, ∼ 370 µ mol mol − 1 ; 200 µ mol mol − 1 above ambient applied by free‐air CO 2 enrichment (FACE)] and soil water (Wet, Dry) on above‐ and below‐ground responses of C 3 (cotton, G ossypium hirsutum ) and C 4 (sorghum, Sorghum bicolor ) plants in monocultures and two density mixtures. In monocultures, CO 2 enrichment increased height, leaf area, above‐ground biomass and reproductive output of cotton, but not sorghum, and was independent of soil water treatment. In mixtures, cotton, but not sorghum, above‐ground biomass and height were generally reduced compared to monocultures, across both CO 2 and soil water treatments. Density did not affect individual plant responses of either cotton or sorghum across the other treatments. Total (cotton + sorghum) leaf area and above‐ground biomass in low‐density mixtures were similar between CO 2 treatments, but increased by 17–21% with FACE in high‐density mixtures, due to a 121% enhancement of cotton leaf area and a 276% increase in biomass under the FACE treatment. Total root biomass in the upper 1.2 m of the soil was not influenced by CO 2 or by soil water in monoculture or mixtures; however, under dry conditions we observed significantly more roots at lower soil depths ( > 45 cm). Sorghum roots comprised 81–85% of the total roots in the low‐density mixture and 58–73% in the high‐density mixture. CO 2 ‐enrichment partly offset negative effects of interspecific competition on cotton in both low‐ and high‐density mixtures by increasing above‐ground biomass, with a greater relative increase in the high‐density mixture. As a consequence, CO 2 ‐enrichment increased total above‐ground yield of the mixture at high density. Individual plant responses to CO 2 enrichment in global change models that evaluate mixed plant communities should be adjusted to incorporate feedbacks for interspecific competition. Future field studies in natural ecosystems should address the role that a CO 2 ‐mediated increase in C 3 growth may have on subsequent vegetation change.

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

The establishment of a network of European human research tissue banks - Samantha Orr; Eliane Alexandre; Brain Clark; Robert Combes; Lueder M. Fels; Neil Gray; Ann-Cathrine Jönsson-Rylander; Heikki Helin; Jukka Koistinen; Teija Oinonen; Lysiane Richert; Rivka Ravid; et al. (Cell and Tissue Banking, 2002)

Long-term sexual allocation in herbivore resistant and susceptible pinyon pine (Pinus edulis) - Neil S. Cobb; Robert T. Trotter; Thomas G. Whitham (Oecologia, 2002)

The Nature and Destiny of Translocated B-Chromosome-Specific Satellite DNA of Rye - Robert Hasterok; Glyn Jenkins; Tim Langdon; R. Neil Jones (Chromosome Research, 2002)

Iron uptake and physiological response of phytoplankton during a mesoscale Southern Ocean iron enrichment - Maria T. Maldonado; Philip W. Boyd; Julie LaRoche; Robert Strzepek; Anya Waite; Andrew R. Bowie; Peter L. Croot; Russell D. Frew; Neil M Price (Limnology and Oceanography, 2001)
Iron supply is thought to regulate primary production in high nitrate, low chlorophyll (HNLC) regions of the sea in both the past and the present. A critical aspect of this relationship is acquisition of iron (Fe) by phytoplankton, which occurs through a complex series of extracellular reactions that are influenced by Fe chemistry and speciation. During the first in situ mesoscale Fe‐enrichment experiment in the Southern Ocean (Southern Ocean iron release experiment [SOIREE]), we monitored the uptake of Fe by three size classes of plankton and their ensuing physiological response to the Fe enrichment. Rates of Fe uptake from both inorganic Fe (Fe′) and organic Fe complexes (FeL) were initially fast, indicative of Fe‐limitation. After Fe enrichment phytoplankton down‐regulated Fe uptake and optimized physiological performance, but by day 12 they had greatly increased their capacity to acquire Fe from FeL. The increase in Fe uptake from FeL coincided with a sixfold decrease in Fe′ that followed the production of Fe‐binding organic ligands. Phytoplankton were able to use organically bound Fe at rates sufficient to maintain net growth for more than 42 d. Adaptation to such shifts in Fe chemistry may contribute to bloom longevity in these polar HNLC waters.

Quantitative proteomic analysis of mouse liver response to the peroxisome proliferator diethylhexylphthalate (DEHP) - Neil Macdonald; Stephan Chevalier; Robert Tonge; Matthew Davison; Rachel Rowlinson; Janice Young; Steve Rayner; Ruth Roberts (Archives of Toxicology, 2001)

Measurements of Ozone Deposition to Vegetation Quantifying the Flux, the Stomatal and Non-Stomatal Components - David Fowler; Chris Flechard; J. Neil Cape; Robert L. Storeton-West; Mhairi Coyle (Water, Air, & Soil Pollution, 2001)

Mouse hepatocyte response to peroxisome proliferators: dependency on hepatic nonparenchymal cells and peroxisome proliferator activated receptor α (PPARα) - Susan Hasmall; Neil James; Kathryn Hedley; Kine Olsen; Ruth Roberts (Archives of Toxicology, 2001)

Oxygen isotope analysis of diatom silica and authigenic calcite from Lake Pinarbasi, Turkey - Melanie Leng; Philip Barnker; Peter Greenwood; Neil Roberts; Jane Reed (Journal of Paleolimnology, 2001)

Establishing realistic restoration targets for nutrient-enriched shallow lakes: linking diatom ecology and palaeoecology at the Attenborough Ponds, U.K. - Carl D. Sayer; Neil Roberts (Hydrobiologia, 2001)

Glossary of aquatic habitat inventory terminology. Compiled by Neil B.Armantrout. Published in 1998 by American Fisheries Society. 150 p. ISBN 1–888569–11–5. Price: US$33.00 (available from: APS Publication Fulfillment, P. O. Box 1020, Sewickley, PA 15143, United States).Studying temperate marine environments— a handbook for ecologists. Edited by MichaelKingsford and ChristopherBattershill. Published in 1998 by Canterbury University Press, Private Bag 4800, Christchurch, New Zealand (email: m.bradstock@cup.canterbury.ac.nz). 344 p., limpbound. ISBN 0–908812–54‐X. Price: NZ$49.95. - Neil Deans; Robert G. Wear (New Zealand Journal of Marine and Freshwater Research, 2000)

Species differences in response to diethylhexylphthalate: suppression of apoptosis, induction of DNA synthesis and peroxisome proliferator activated receptor alpha-mediated gene expression - Susan C. Hasmall; Neil H. James; Neil Macdonald; Anthony R. Soames; Ruth A. Roberts (Archives of Toxicology, 2000)

Paleoclimatology - Reconstructing Cimates of the Quaternary. R.S. Bradley - Neil Roberts (Journal of Paleolimnology, 2000)

Field Method for Biosolids N Mineralization Using Porous Ceramic Cups - Charles Henry; Mike Van Ham; Mark Grey; Neil Cowley; Robert Harrison (Water, Air, & Soil Pollution, 2000)

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Neil Macdonald; Douglas West; Stephan Chevalier; Sabina C. Cosulich; Ruth A. Roberts (Archives of Toxicology, 1999)

Distribution and population dynamics of Porphyra (Bangiales, Rhodophyta) in the southern Western Cape, South Africa - Neil J. Griffin; John J. Bolton; Robert J. Anderson (Journal of Applied Phycology, 1999)

Late Quaternary palaeohydrology of the Konya Basin, Turkey, based on isotope studies of modern hydrology and lacustrine carbonates - Melanie J. Leng; Neil Roberts; Jane M. Reed; Hilary J. Sloane (Journal of Paleolimnology, 1999)

Long-term remission of Crohn's disease treated with thalidomide: A seminal case report - Steven J. Fishman; Neil R. Feins; Robert J. D'Amato; Judah Folkman (Angiogenesis, 1999)

Long‐term dynamics of algal and invertebrate communities in a small, fluctuating tropical soda lake - Dirk Verschuren; Christine Cocquyt; John Tibby; C. Neil Roberts; Peter R. Leavitt (Limnology and Oceanography, 1999)
Lake Sonachi, Kenya, is a small alkaline‐saline crater lake that over the past 175 years has experienced considerable fluctuations in lake depth (Zmax = 3–18 m) and an alternation of meromictic and holomictic episodes lasting from a few years to several decades. Paleolimnological methods were used to reconstruct the long‐term dynamics of algal and invertebrate communities in Lake Sonachi in relation to the historical evolution of their physical and chemical environment. Multivariate statistical analysis revealed only weak correlation between the stratigraphic distributions of fossil algal pigments, diatoms, and chironomid larvae in 210Pb‐dated sediment cores and the documented or reconstructed variation in lake depth, mixing regime, and surface‐water conductivity. The eventful biological history of Lake Sonachi exemplifies the complexity of long‐term community dynamics in tropical African soda lakes and reveals how phytoplankton community structure can exert direct control on benthic and planktonic invertebrate communities. The modest phytoplankton abundance and photosynthetic activity of Lake Sonachi when compared with other tropical African soda lakes represent recent lake conditions, resulting from a dramatic decline of filamentous cyanobacteria (e.g., Spirulina platensis) between the 1930s and 1970s and incomplete replacement by the small coccoid cyanobacteria (e.g., Synechococcus bacillaris), which are dominant today. This reduction in algal biomass favored benthic and planktonic invertebrates by reducing the prevalence of complete water‐column anoxia associated with intense nighttime respiration of cyanobacterial blooms. Anoxia‐intolerant halobiont chironomids expanded during an episode of low lake level (Zmax 9,000 µS cm −1 ) in the late 1940s and 1950s, whereas they had failed to do so under similar conditions in the late 19th century when algal abundance was high. Planktonic cladocerans developed high population densities only during two short meromictic phases in the 1970s when conductivity was modest (3,000–6,000 µS cm −1 ) and algal abundance was low. The decline of filamentous cyanobacteria also increased water‐column transparency but apparently did not increase benthic diatom abundance.

Determining optical absorption of colored dissolved organic matter in seawater with a liquid capillary waveguide - Eurico J. D'Sa; Robert G. Steward; Anthony Vodacek; Neil V. Blough; Dave Phinney (Limnology and Oceanography, 1999)
Optical absorption spectra of 0.2‐μm filtered sea‐water samples originating from diverse oceanic and coastal waters were measured with a long pathlength capillary wave‐guide; results were compared with those of three different lab‐oratory spectrophotometers. The 0.5‐m long 550‐ µm (inside diameter) aqueous waveguide uses only 120 ml of filtered sea‐water, making it convenient for use in flow‐through cells or when sample volumes are restricted. Source light propagates inside the capillary waveguide by total internal reflection because of the lower refractive index of the waveguide walls with respect to the aqueous core. The absorption coefficient of colored dissolved organic matter (CDOM) at 355 nm and S , the slope of the log linearized CDOM absorption spectra, were determined for all samples. The CDOM absorption spec‐tra measured by the capillary waveguide closely matched that measured by spectrophotometers for CDOM concentrations varying over an order of magnitude. The deviations between the absorption spectra obtained with the capillary waveguide and those obtained with the standard spectrophotometers increased with decreasing total absorption and with increase in wavelength, presumably because of the greater baseline offsets observed in the capillary waveguide. The offsets are due to differences in refractive indices between the seawater samples and the freshwater reference. With a suitable reference, the capillary waveguide will be very useful for monitoring surface seawater CDOM absorption semicontinuously.

Changes in Climate Extremes Over the Australian Region and New Zealand During the Twentieth Century - Neil Plummer; M. James Salinger; Neville Nicholls; Ramasamy Suppiah; Kevin J. Hennessy; Robert M. Leighton; Blair Trewin; Cher M. Page; Janice M. Lough (Climatic Change, 1999)

Lake evolution in a semi-arid montane environment: response to catchment change and hydroclimatic variation - Henry Lamb; Neil Roberts; Melanie Leng; Philip Barker; Abdelfattah Benkaddour; Sander van der Kaars (Journal of Paleolimnology, 1999)

Mangrove transgression into saltmarsh environments in south‐east Australia - Neil Saintilan; Robert J. Williams (Global Ecology and Biogeography, 1999)
The landward transgression of man‐ groves into saltmarsh environments in the estuaries of south‐east Australia over the last five decades is established as a widespread trend through a review of a number of independent studies. This process is occurring in a range of geomorphic settings, and in some cases reversing the direction of longer‐term vegetation change. Several hypotheses are advanced to explain this occurrence, including increases in rainfall, revegetation of areas cleared for agriculture, altered tidal regimes or estuary water levels, and increases in nutrient levels and sedimentation.

Suppression of hepatocyte apoptosis and induction of DNA synthesis by the rat and mouse hepatocarcinogen diethylhexylphlathate (DEHP) and the mouse hepatocarcinogen 1,4-dichlorobenzene (DCB) - Neil H. James; Anthory R. Soames; Ruth A. Roberts (Archives of Toxicology, 1998)

The peroxisome proliferator nafenopin does not suppress hepatocyte apoptosis in guinea-pig liver in vivo nor in human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Anthony R. Soames; Ruth A. Roberts (Archives of Toxicology, 1998)

210 Pb chronology from Wellington Harbour, New Zealand - James R. Goff; Neil E. Whitehead; Robert G. Ditchburn (New Zealand Journal of Marine and Freshwater Research, 1998)
A sediment accumulation record based on the levels of “unsupported” 210 Pb was obtained from a core taken from the centre of Wellington Harbour, New Zealand. Sediment accumulation rates (SARs) varied from 3 to 5 mm yr ‐1 . Before 1920, SARs were sufficiently high to dilute unsupported levels of 210 Pb to background, but had fallen below the mean by 1925 maintaining constant SARs until 1953. These data provide a higher resolution chronology of early 20th century SARs than was previously available. Comparison with 137 Cs data confirms that there was a significant increase in SARs between 1953 and 1967, but that these have remained fairly constant since 1974. Data from the two radionuclides are consistent after 1974, and 210 Pb data are consistent with other chronological measurements before 1953. Therefore, it is suggested that the two radionuclides are immobile in the marine sediments of Wellington Harbour and that differences between the two SARs are real.

A peroxisome proliferator-activated receptor-alpha (PPARα) cDNA cloned from guinea-pig liver encodes a protein with similar properties to the mouse PPARα: implications for species differences in responses to peroxisome proliferators - Jonathan D. Tugwood; Peter R. Holden; Neil H. James; Rebecca A. Prince; Ruth A. Roberts (Archives of Toxicology, 1998)

Seasonal variation of CDOM and DOC in the Middle Atlantic Bight: Terrestrial inputs and photooxidation - Anthony Vodacek; Neil V. Blough; Michael D. DeGrandpre; Michael D. DeGrandpre; Robert K. Nelson (Limnology and Oceanography, 1997)
Extensive surveys of the fluorescence and absorption of chromophore‐containing dissolved organic matter (CDOM), dissolved organic C (DOC) concentration, chlorophyll fluorescence, and salinity were performed during August and November 1993 and March and April 1994 along a cruise line extending from the mouth of Delaware Bay southeast to the Sargasso Sea. With shallow stratification in August, photobleaching dramatically altered the optical properties of the surface waters, with ∼70% of the CDOM absorption and fluorescence lost through photooxidation in the waters at the outer shelf. S , the slope of the log‐linearized absorption spectrum of CDOM, increased offshore and seemed to increase with photodegradation. The increase in S combined with the seasonal variation in the relationship between Chl and CDOM underscores the difficulty in developing algorithms to predict Chl concentrations in turbid coastal waters with ocean color data. Despite the photooxidation of CDOM, the seasonal variation in the CDOM fluorescence‐absorption relationship and fluorescence quantum yields was

Nordonna: A red-skinned potato cultivar with wide adaptability - Richard G. Novy; Robert H. Johansen; Gary A. Secor; Bryce L. Farnsworth; Jim H. Lorenzen; Neil C. Gudmestad; Edna T. Holm (American Journal of Potato Research, 1997)

Goldrush: A new high quality russet-skinned potato cultivar - Robert H. Johansen; Bryce Farnsworth; Gary A. Secor; Neil C. Gudmestad; Asunta Thompson-Johns; Edna T. Holm (American Journal of Potato Research, 1994)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

The Role of Episodic Atmospheric Nutrient Inputs in the Chemical and Biological Dynamics of Oceanic Ecosystems - Percy Donaghay; Peter Liss; Robert Duce; Dana Kester; Alfred Hanson; Tracy Villareal; Neil Tindale; Dian Gifford (Oceanography, 1991)

Competition betweenBracon mellitor [Hym.: Braconidae] andCatolaccus grandis [Hym.: Pteromalidae] for their hostAnthonomus grandis [Col.: Curculionidae] - Robert J. O'neil; James R. Cate (BioControl, 1985)

Developmental toxicity of Guthion in rats and mice - Robert D. Short; Jan L. Minor; Cheng-Chun Lee; Neil Chernoff; Ronald L. Baron (Archives of Toxicology, 1980)